Laminated film and film laminate

JP2025027158AInactive Publication Date: 2025-02-27MITSUBISHI CHEM CORP

Patent Information

Application Number
JP2021208794
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-22
Publication Date
2025-02-27
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025027158000001_ABST
    Figure 2025027158000001_ABST
Patent Text Reader

Abstract

To provide a laminated film and a film laminate which are suitable for the application of transferring an uneven shape onto an adherend.SOLUTION: A laminated film includes a curable resin layer on one surface of a base material film (A), in which the curable resin layer has an uneven structure, an arithmetic mean height (Sa) of the surface of the curable resin layer is 500 nm or more, in a distribution curve in which a horizontal axis represents a projection height (X) and a vertical axis represents a common logarithm value log (Y) of the number (Y) of projections, which are obtained from a surface profile obtained from surface observation of the curable resin layer by a white interference microscope, the curable resin layer satisfies the expression (1). In the expression, log (Y) max represents a value for which the common logarithm of the number of projections becomes maximum, and Xmax represents a positive projection height when the common logarithm of the number of projections becomes maximum. Log (Y) 85% represents a value that the common logarithm of the number of projections becomes 85% of the maximum value, and X85% represents a positive projection height when the common logarithm of the number of projections becomes 85% of the maximum value.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate film and a film laminate. [Background technology]

[0002] Conventionally, polyester films, particularly polyethylene terephthalate films and polyethylene naphthalate films, have excellent mechanical properties, heat resistance, and chemical resistance, and have been used in a variety of applications, such as packaging, electronic parts, electrical insulation, metal lamination, optical applications such as display components for foldable displays, bendable displays, and rollable displays, touch panels, anti-reflection, and glass shatter prevention.

[0003] These polyester films, which are used in a wide range of applications, can be used to protect adhesive layers of glass, steel plates, etc. that are used mainly outdoors, such as in buildings, automobiles, trains, and airplanes.

[0004] When a substrate film with an adhesive layer is attached to an adherend such as glass or an automobile body, air or moisture may remain at the interface between the adhesive layer and the adherend after lamination, causing air bubbles of several hundred microns in size that can be seen with the naked eye, resulting in poor appearance, or a decrease in adhesive strength due to residual moisture.

[0005] As a countermeasure, the occurrence of the above-mentioned problems has been prevented by spraying water or an aqueous solution containing a surfactant onto the surface of the adhesive layer in advance and then using a squeegee to remove water or bubbles, a process known as "water lamination."

[0006] Under such circumstances, a release liner has been proposed that has a fine embossed pattern composed of a large number of interconnected linear ridges on one surface, with the aim of forming fine grooves on the adhesive surface to allow fluid to flow out at the adhesive interface (Patent Document 1). In addition, as a pressure-sensitive adhesive sheet that has excellent air release properties that allow air pockets that may occur when the sheet is attached to an adherend to be easily removed and also has good adhesive properties, a pressure-sensitive adhesive sheet has been proposed that has a resin layer on a substrate or release material, the surface of the resin layer opposite the substrate or release agent has adhesive properties, and irregularly shaped recesses exist on the surface (Patent Document 2). Furthermore, a coating protection film for automobiles has been proposed that has a pressure-sensitive removable adhesive layer on the vehicle body surface side and a plastic film on the outside, and has a centerline average roughness (Ra) of 0.1 to 100 μm on the surface (Patent Document 3). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2006-70273 A [Patent Document 2] International Publication No. 2015 / 152352 [Patent Document 3] Japanese Patent Application Publication No. 7-89468 Summary of the Invention [Problem to be solved by the invention]

[0008] The above-mentioned "water application" method requires skilled techniques to remove water and bubbles using a squeegee. In recent years, with the expansion of the market for wrapping printed adhesive films for automobiles, trucks, trains, and airplanes, and for PPF (paint protection film) applications for protecting automobile paintwork, for example, 2 When applying such a large-area adhesive film to an adherend, it has become increasingly difficult to apply it uniformly. In addition, when applying the film by wet application, it is necessary to prevent air pockets from forming during application to the adherend. Furthermore, the techniques disclosed in the above Patent Documents 1 to 3 are insufficient in terms of removing moisture or bubbles, or removing "air pockets" that occur when attaching the tape to an adherend (air removal). The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide a laminate film and a film laminate suitable for use in transferring a concave-convex shape to an adherend. [Means for solving the problem]

[0009] As a result of intensive research in light of the above circumstances, the present inventors have found that the above problems can be easily solved by using a laminate film having a specific configuration, and have thus completed the present invention.

[0010] That is, the gist of the present invention provides the following [1] to

[26] .

[0011] [1] A laminate film comprising a cured resin layer on one side of a base film (A), the cured resin layer having an uneven structure, the cured resin layer having an arithmetic mean height (Sa) of a surface of 500 nm or more, and a distribution curve obtained from observation of the surface of the cured resin layer with a white light interference microscope, the horizontal axis being the projection height (X) and the vertical axis being the common logarithm of the number of projections (Y), wherein the cured resin layer satisfies the following formula (1):

number

number

number

[10] The laminate film according to any one of the above [1] to [9], wherein the cured resin layer has a maximum peak height (Sp) of 10,000 nm or more on the surface.

[11] The laminate film according to any one of the above [1] to

[10] , wherein the gloss of the surface of the cured resin layer at 60 degrees is 10% or less.

[12] The laminate film according to any one of the above [1] to

[11] , wherein the gloss of the surface of the cured resin layer at an angle of 85 degrees is 15% or less.

[13] The laminate film according to any one of the above [1] to

[12] , wherein the cured resin layer is a cured product of a curable resin composition containing a (meth)acrylate.

[14] The method for producing the laminated film according to any one of the above [1] to

[13] , comprising the step of forming the cured resin layer by irradiation with an excimer lamp or ultraviolet (UV) light.

[15] A release film comprising a cured resin layer of the laminate film according to any one of the above [1] to

[13] , and a release layer on the cured resin layer.

[16] The release film according to

[15] above, wherein the release layer contains at least one release agent selected from the group consisting of silicone compounds, melamine compounds, fluorine compounds, waxes and long-chain alkyl compounds.

[17] A film laminate comprising the release film according to

[15] or

[16] above and an adhesive layer on the release layer surface of the release film.

[18] A film laminate comprising the laminate film according to any one of the above [1] to

[13] and an adhesive layer on the surface of the cured resin layer of the laminate film.

[19] A transferred product having the projections and recesses on the surface of the cured resin layer of the laminate film according to any one of the above [1] to

[13] .

[20] A transfer product to which the irregularities on the surface of the release layer of the release film described in

[15] or

[16] above have been transferred.

[21] The film laminate according to

[17] or

[18] above, wherein the adhesive layer is at least one selected from the group consisting of an acrylic adhesive layer, a urethane adhesive layer, and a silicone adhesive layer.

[22] The laminate film according to any one of the above [1] to

[13] , which is for protecting an adhesive layer.

[23] The release film according to

[15] or

[16] above, which is for protecting an adhesive layer.

[24] The laminate film according to any one of the above [1] to

[13] and

[22] , which is used for protecting automobile paint or as a wrapping film.

[25] The release film according to any one of the above

[15] ,

[16] and

[23] , which is used for automobile paint protection or as a wrapping film.

[26] The film laminate according to

[17] or

[18] above, which is used for automobile paint protection or as a wrapping film. Effect of the Invention

[0012] According to the present invention, it is possible to provide a laminate film and a film laminate that are suitable for applications in which a concave-convex shape is transferred to an adherend. Specifically, it is possible to provide a laminated film and a film laminate that, when applied to an adherend by wet application or the like, leaves minimal moisture or bubbles, and minimizes air pockets during application, and is easy to cut into individual sheets, and is of high industrial value, particularly suitable for use as an automobile painting or wrapping film. [Brief description of the drawings]

[0013] [Figure 1] 2 is a bird's-eye view of the surface of a cured resin layer of the laminate film obtained in Example 1. [Diagram 2] 4 is a bird's-eye view of the surface of a cured resin layer of the laminated film obtained in Example 3. [Diagram 3] 3 is a bird's-eye view of the surface of a cured resin layer of the laminate film obtained in Comparative Example 1. [Figure 4] 4 is a bird's-eye view of the surface of a cured resin layer of the laminated film obtained in Comparative Example 4. [Diagram 5] FIG. 13 is a three-dimensional bird's-eye view showing the state of a positive protrusion and a negative protrusion. [Figure 6] 4 is a distribution curve showing the relationship between the projection height and the number of projections in the laminated film obtained in Example 1. [Figure 7] 4 is a distribution curve showing the relationship between the projection height and the number of projections in the laminated film obtained in Example 3. [Figure 8] 4 is a distribution curve showing the relationship between the projection height and the number of projections in the laminated film obtained in Comparative Example 1. [Figure 9] 4 is a distribution curve showing the relationship between the projection height and the number of projections in the laminated film obtained in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The laminated film of the present invention comprises a cured resin layer having an uneven structure on one side of a base film. Each of the constituent elements will be described in detail below.

[0015] [Base film] An example of the substrate film is a resin film. Examples of the resin film include polyethylene, polypropylene, cycloolefin polymer (COP), polyester, polystyrene, acrylic resin, polycarbonate, polyurethane, triacetyl cellulose (TAC), polyvinyl chloride, polyethersulfone, polyamide, polyimide, polyamideimide, etc. If it is possible to form a film, it may be a mixture of these materials (polymer blend) or a composite of the structural units (copolymer).

[0016] Among the above-mentioned films, polyester film is particularly preferred because it has excellent physical properties such as heat resistance, flatness, optical properties, and strength. The base film (A), for example, polyester film, may be a single-layer structure or a multi-layer structure, and may be a multi-layer structure of four or more layers other than two or three layers as long as it does not exceed the gist of the present invention, and is not particularly limited. It is preferable that the base film (A) is a multi-layer structure of at least two or more layers, each of which has its own characteristics, and is multifunctional.

[0017] The polyester used in the polyester film can be obtained by polycondensation of a dicarboxylic acid and a diol, and preferably obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid. Examples of the aliphatic glycol include ethylene glycol, diethylene glycol, trimethylene glycol, tetramethylene glycol, and neopentyl glycol. The aliphatic glycol may be an alicyclic glycol such as 1,4-cyclohexanedimethanol.

[0018] Representative examples of polyesters include polyethylene terephthalate (PET), polyethylene-2,6-naphthalenedicarboxylate (PEN), polybutylene terephthalate, and the like. Such polyesters may be homopolymers that are not copolymerized. Alternatively, they may be copolymerized polyesters in which 30 mol % or less of the dicarboxylic acid components are dicarboxylic acid components other than the main component and / or 30 mol % or less of the diol components are diol components other than the main component. For example, polyethylene terephthalate may be a copolymerized polyester that has about 30 mol % or less of dicarboxylic acid units other than terephthalic acid out of 100 mol % of dicarboxylic acid units, and has about 30 mol % or less of diol units other than ethylene glycol out of 100 mol % of diol units. The polyester may also be a mixture of homopolymer and copolymer polyesters.

[0019] The intrinsic viscosity of the polyester is not particularly limited, but from the viewpoints of film-forming properties, productivity, and the like, it is preferably 0.45 to 1.0 dL / g, and more preferably 0.5 to 0.9 dL / g.

[0020] The polyester can be obtained by a conventionally known method, for example, a method of directly obtaining a low-polymerization polyester by reacting a dicarboxylic acid with a diol, or a method of reacting a lower alkyl ester of a dicarboxylic acid with a diol using a conventionally known transesterification catalyst, followed by polymerization reaction in the presence of a polymerization catalyst. As the polymerization catalyst, known catalysts such as antimony compounds, germanium compounds, titanium compounds, etc. may be used, but it is preferable to use a catalyst other than an antimony compound. Alternatively, when an antimony compound is used, it is preferable to set the amount of the antimony compound to 100 ppm or less as antimony element, since this can further reduce the dullness of the film.

[0021] Furthermore, when a titanium compound is used as a catalyst, the amount of titanium used can be reduced due to the high activity of titanium, and the amount of metal remaining in the film is small, which is preferable from the standpoint of film transparency and reducing the generation of foreign matter.

[0022] In the laminated film of the present invention, the cured resin layer described below needs to satisfy specific parameters regarding its surface roughness. The method for satisfying the specific parameters is not particularly limited, but an example of the method is to include particles in the base film. It is preferable to incorporate particles into the base film so that the cured resin layer surface can have the desired arithmetic mean height (Sa) and maximum peak height (Sp), which will be described in detail later, and further so that the projection height (X) and the number of projections (Y) on the cured resin layer surface satisfy the formula (1), which will be described later. The type of particles to be blended is not particularly limited as long as it is a particle that can impart the above-mentioned properties, and examples thereof include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as (meth)acrylic resins, styrene resins, urea resins, phenolic resins, epoxy resins, and benzoguanamine resins. Furthermore, when the base film is a polyester film, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used. Among these, silica particles, calcium carbonate particles, and (meth)acrylic resin particles are preferred because they are particularly effective in small amounts.

[0023] The shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. There are also no particular limitations on the hardness, specific gravity, color, etc. of the particles. One type of these particles may be used alone, or two or more types may be used in combination as necessary.

[0024] The average particle size of the particles used is preferably in the range of 1 to 10 μm, more preferably in the range of 1 to 8 μm, even more preferably in the range of 2 to 6 μm, and particularly preferably in the range of 2 to 5 μm, in order to improve the water drainage or bubble drainage effect, or, as described below, in an embodiment in which the laminated film of the present invention has an adhesive layer, in order to improve the air drainage effect when the film is attached to an adherend.

[0025] In the case of a monolayer film, the particle content in the base film is preferably in the range of 0.1 to 10% by mass based on the total polyester constituting the film. When the particle content is 0.1% by mass or more, sufficient effects of water removal or bubble removal, or, as described below, air removal during lamination to an adherend in an embodiment in which the laminated film of the present invention has an adhesive layer, are obtained, and when the particle content is 10% by mass or less, the productivity of the base film is ensured. From the above viewpoints, the particle content in the base film is more preferably in the range of 0.3 to 10% by mass, even more preferably 0.4 to 10% by mass, even more preferably 0.4 to 8% by mass, and particularly preferably 3 to 6% by mass.

[0026] In addition, when the base film is a multi-layer film, the surface layer may contain particles having a predetermined content and particle size. For example, when the base film is a polyester film, the polyester film may be provided with a polyester layer containing particles only on the surface layer, which allows sufficient unevenness to be formed and prevents a decrease in productivity due to the addition of particles. In any case, the layer in contact with the cured resin layer may contain particles. That is, in the laminate film of the present invention, the base film provides a sufficient effect of removing water or bubbles from the surface layer on the side in contact with the cured resin layer, or, as described below, in an embodiment in which the laminate film of the present invention has an adhesive layer, removing air when attached to an adherend, and from the viewpoint of productivity of the base film, the particle content is preferably 0.1 to 10 mass%, more preferably 0.3 to 10 mass%, even more preferably 0.4 to 10 mass%, still more preferably 0.4 to 8 mass%, and particularly preferably in the range of 3 to 6 mass%. The average particle size of the particles is the same as that of the particles in the case of the single layer described above.

[0027] The method of adding particles to the base film is not particularly limited, and any conventionally known method can be adopted.For example, when the base film is a polyester film, the particles can be added at any stage of polyester production, but preferably, the particles can be added at the stage of esterification or after the completion of the transesterification reaction, and the polycondensation reaction can be carried out. Alternatively, a method in which a slurry in which the particles are dispersed in ethylene glycol or water is blended with the polyester raw material using a kneading extruder with a vent, or a method in which dried particles are blended with the polyester raw material using a kneading extruder, etc. can be used.

[0028] In addition to the above-mentioned particles, the base film may contain conventionally known antioxidants, heat stabilizers, lubricants, antistatic agents, fluorescent brighteners, dyes, fillers (inorganic or organic fillers), pigments, etc., depending on the purpose of the ultraviolet protection film base material, the glass application to be protected, and the prevention of deterioration of the coating film of the body such as a steel plate, etc., an ultraviolet absorber, particularly a benzoxazinone-based ultraviolet absorber, may be contained.

[0029] From the viewpoint of using the laminate film of the present invention as a release film, the thickness of the base film is preferably in the range of 20 to 350 μm, more preferably 20 to 250 μm, even more preferably 25 to 125 μm, particularly preferably 25 to 100 μm, and especially preferably 25 to 60 μm. When the base film has a multi-layer structure, the total thickness is within the above range.

[0030] The polyester film can be laminated by using various conventional methods such as coextrusion. In this case, the thickness of the outermost layer is preferably 2 μm or more, more preferably 3 μm or more, on one side only, and is preferably 1 / 8 or less of the total thickness. By setting the thickness in the above range, as described above, it is possible to manufacture a polyester film having a polyester layer containing particles only on the surface layer, and to form sufficient irregularities and to avoid a decrease in productivity due to particles.

[0031] In the laminated film, the arithmetic mean height (Sa) of the substrate film surface on the side where the cured resin layer is formed is preferably 5 nm or more, more preferably 10 nm or more, even more preferably 100 nm or more, particularly preferably 400 nm or more, and particularly preferably 600 nm or more. By making the surface roughness of the polyester film in contact with the lower part of the cured resin layer to be equal to or more than the above numerical value, more suitable performance of the laminated film of the present invention can be easily obtained.

[0032] Hereinafter, a production method in which the base film (A) is a polyester film will be specifically explained, but the present invention is not particularly limited to the following examples as long as they satisfy the gist of the present invention. In general, first, undried or dried polyester chips are fed into a melt extrusion device by a known method, and heated to a temperature equal to or higher than the melting point of each polymer to melt it. The molten polymer is then extruded from a die and rapidly cooled to a temperature equal to or lower than the glass transition temperature on a rotating cooling drum to obtain a substantially amorphous unoriented sheet. In this case, in order to improve the flatness of the sheet, it is preferable to increase the adhesion between the sheet and the rotating cooling drum, and in the present invention, an electrostatic application adhesion method and / or a liquid application adhesion method are preferably adopted.

[0033] From the viewpoint of film strength, it is preferable to biaxially stretch the sheet obtained as described above to form a film. Specifically, the stretching conditions are as follows: the unstretched sheet is stretched in the longitudinal direction (machine direction) at 70 to 145°C, preferably 80 to 120°C, at a stretch ratio of 2.0 to 4.5 times, preferably 3.0 to 4.0 times, to form a uniaxially stretched film. Next, the film is stretched in the transverse direction (width direction) perpendicular to the longitudinal direction (machine direction) at a stretching ratio of 3.0 to 6.5 times or 3.5 to 6.0 times at 90 to 160° C. to obtain a biaxially stretched film. Subsequently, it is preferable to carry out a heat treatment (heat setting) for 10 to 600 seconds under tension or relaxation of 30% or less at 210 to 260° C. Then, it is preferable to relax the film by 1 to 10% in the longitudinal and / or transverse directions in the maximum temperature zone of the heat treatment and / or in the cooling zone at the exit of the heat treatment. The longitudinal direction (machine direction) of the film refers to the direction in which the film advances during the film manufacturing process, i.e., the direction in which the film roll is wound. The transverse direction (width direction) refers to the direction parallel to the film surface and perpendicular to the longitudinal direction, i.e., the direction parallel to the central axis of the roll when the film is in a roll shape.

[0034] In particular, when used in applications where the heat shrinkage rate needs to be kept low, the heat treatment temperature is preferably 215 to 250° C., more preferably 220 to 245° C., and further preferably 230 to 245° C. By setting the heat treatment temperature within the above temperature range, it is possible to minimize the heat shrinkage rate.

[0035] In particular, the laminated film of the present invention is suitable for protecting adhesive layers used on glass, steel plates, etc. that are used mainly outdoors, such as for automobiles, signs, solar power generation, road-related members such as road signs and sound insulation walls, etc.

[0036] [Cured resin layer] The laminate film of the present invention comprises a cured resin layer on one side of the above-mentioned base film (A). The curable resin composition that forms the cured resin layer preferably contains an active energy ray-curable compound.

[0037] By irradiating the cured resin composition with active energy rays, the surface side of the cured resin layer (coating film when the cured resin layer is formed by coating) formed from the cured resin composition is cured first to form a cured coating. After that, when the inside of the cured resin layer (coating film) is cured, the cured resin layer (cured coating film) on the surface side buckles, forming a cured film having an uneven surface. The cured resin layer composition may further contain an organic solvent, if necessary. The cured resin layer composition may further contain other components in addition to those described above, as necessary.

[0038] As the active energy ray-curable compound, a (meth)acrylate is preferable. That is, in one embodiment of the present invention, the cured resin layer is preferably a cured product of a curable resin composition containing a (meth)acrylate. In this specification, the term "(meth)acrylate" means either or both of "acrylate" and "methacrylate". Similarly, the term "(meth)acrylic acid" means either or both of "acrylic acid" and "methacrylic acid", and the term "(meth)acryloyl" means either or both of "acryloyl" and "methacryloyl".

[0039] The (meth)acrylate is not particularly limited, and one of monofunctional (meth)acrylates, bifunctional (meth)acrylates, and polyfunctional (meth)acrylates, or a mixture of two or more of these, a commercially available curable resin material, or a material to which other components have been further added can be used as long as the purpose of this embodiment is not impaired. Among these, monofunctional or bifunctional (meth)acrylates are preferred from the viewpoint of easily forming a steep uneven structure. For applications requiring scratch resistance, bifunctional (meth)acrylates are more preferred. The use of polyfunctional (meth)acrylates is preferred in terms of improving scratch resistance and hardness, but depending on the compound used, it may be difficult to form an uneven structure, so attention must be paid to the type of compound used and the blending ratio. For example, when a urethane-based (meth)acrylate is used as the polyfunctional (meth)acrylate, the amount of the urethane-based (meth)acrylate out of 100 mass% of the (meth)acrylate resin contained in the cured resin layer will vary depending on the resin composition of the cured resin layer, but is preferably 50 mass% or less, and more preferably 30 mass% or less, so that the surface of the cured resin layer can be easily deformed to an appropriate degree and the desired uneven structure can be properly formed. Furthermore, by using a polyfunctional (meth)acrylate having three or more functional groups, excluding the urethane-based (meth)acrylate, in an amount, for example, of 25 mass % or more, more preferably 35 mass % or more, which varies depending on the resin composition of the cured resin layer, it is possible to impart an appropriate hardness to the cured resin layer, thereby appropriately forming the desired uneven structure.

[0040] The bifunctional (meth)acrylate is not particularly limited, but examples thereof include 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,Alkanediol di(meth)acrylates such as 9-nonanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, isobornyl di(meth)acrylate, tricyclodecanediol di(meth)acrylate, adamantyldiol di(meth)acrylate, etc.; bisphenol A di(meth)acrylate, bisphenol A ethylene oxide modified di(meth)acrylate, etc.; bisphenol A caprolactone modified di(meth)acrylate, etc. ) acrylate, bisphenol A glycidyl ether modified di(meth)acrylate, bisphenol F di(meth)acrylate, bisphenol F caprolactone modified di(meth)acrylate, bisphenol F alkylene oxide modified di(meth)acrylate such as bisphenol F ethylene oxide modified di(meth)acrylate, bisphenol modified di(meth)acrylate such as bisphenol F glycidyl ether modified di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate, hydrogenated bisphenol A acrylate Hydrogenated bisphenol-modified di(meth)acrylates such as alkylene oxide-modified di(meth)acrylate, hydrogenated bisphenol A caprolactone-modified di(meth)acrylate, hydrogenated bisphenol A glycidyl ether-modified di(meth)acrylate, hydrogenated bisphenol F di(meth)acrylate, hydrogenated bisphenol F caprolactone-modified di(meth)acrylate, hydrogenated bisphenol F alkylene oxide-modified di(meth)acrylate, hydrogenated bisphenol F glycidyl ether-modified di(meth)acrylate, and polyethylene glycol Examples of the di(meth)acrylate include polyalkylene glycol di(meth)acrylates such as ricol di(meth)acrylate and polypropylene glycol di(meth)acrylate, glycerin di(meth)acrylate, urethane di(meth)acrylate, epoxy di(meth)acrylate, fluorene di(meth)acrylate, fluorene alkylene oxide modified di(meth)acrylate, dioxane glycol di(meth)acrylate, isosorbide di(meth)acrylate, and isosorbide alkylene oxide modified di(meth)acrylate. Among these, in consideration of the ease of forming an uneven structure, a structure without branching is preferable, alkyldiol di(meth)acrylate or glycerin di(meth)acrylate is more preferable, and alkyldiol di(meth)acrylate having 4 to 18 carbon atoms is even more preferable.

[0041] The monofunctional (meth)acrylate is not particularly limited, and examples thereof include methyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, cyclopentyl (meth)acrylate, 1-methylcyclopentyl (meth)acrylate, 1-ethylcyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 1-methylcyclohexyl (meth)acrylate, 1-ethylcyclohexyl (meth)acrylate, and the like. alkyl (meth)acrylates such as butyl methacrylate, trimethylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, 2-cyclohexylpropanyl (meth)acrylate, adamantyl (meth)acrylate, 2-methyladamantyl (meth)acrylate, 2-ethyladamantyl (meth)acrylate, and 2-isopropyladamantyl (meth)acrylate; hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, and ethoxypropyl (meth)acrylate; aromatic (meth)acrylates such as phenyl (meth)acrylate; aromatic group-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate; amino group-containing (meth)acrylates such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate. Acrylates, methoxyethylene glycol (meth)acrylates, phenoxypolyethylene glycol (meth)acrylates, ethylene oxide modified (meth)acrylates such as phenylphenol ethylene oxide modified (meth)acrylates, glycidyl (meth)acrylates, tetrahydrofurfuryl (meth)acrylates, phenyl alkylene oxide modified (meth)acrylates, nonylphenol (meth)acrylates, nonylphenol alkylene oxide modified (meth)acrylates, phenoxybenzyl (meth)acrylates,Phenylbenzyl (meth)acrylate, biphenyl (meth)acrylate, biphenyl alkylene oxide modified (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentanyl alkylene oxide modified (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, dicyclopentenyl alkylene oxide modified (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, (2-oxo-1,3-dioxolan-4-yl)methyl (meth)acrylate, mevalonic acid lactone (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, (3,4-epoxycyclohexyl)methyl (meth)acrylate, and the like. Among these, a ring structure is preferable in view of the ease of forming a steep uneven structure.

[0042] The trifunctional or higher polyfunctional (meth)acrylate is not particularly limited, and examples thereof include ethylene oxide-modified poly(meth)acrylates such as dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, and ethylene oxide-modified pentaerythritol tetra(meth)acrylate, glycerin tri(meth)acrylate, and the like. Examples of the urethane acrylate include (meth)acrylate, isocyanuric acid ethylene oxide modified tri(meth)acrylate, isocyanuric acid modified tri(meth)acrylate such as ε-caprolactone modified tris(acryloxyethyl)isocyanurate, pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, condensate of isophorone diisocyanate and dipentaerythritol pentaacrylate, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, etc. Among these, in consideration of the ease of forming an uneven structure, ethylene oxide modified type and trifunctional (meth)acrylate are preferred.

[0043] The cured resin layer composition may contain active energy ray curable compounds other than (meth)acrylates, such as vinyl compounds, such as styrene, vinyl halides, and vinyl acetate, and diene compounds, such as vinylidene halides, acrylamide, vinylamide, (meth)acrylonitrile, 1,3-butadiene, isoprene, and chloroprene.

[0044] When an active energy ray curable compound is used in the formation of the cured resin layer, its content in the cured resin composition is preferably 5% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 50% by mass or more, and most preferably 60% by mass or more in the non-volatile content of the curable resin composition. There is no particular upper limit and it may be 100% by mass, but it is preferably 99% by mass or less, more preferably 98% by mass or less. When the content of the active energy ray curable compound in the cured resin composition is in the above range, it is easy to form an uneven structure, and a cured film having excellent hardness and scratch resistance can be formed, and an appropriate uneven structure can be obtained.

[0045] In order to improve the adhesion between the cured resin layer and the base film (A), various resins can be further added to the cured resin composition. As the resin, various conventionally known resins can be used, for example, acrylic resin, polyester resin, polyurethane resin, polyvinyl resin, etc. Among these, acrylic resin is preferable in terms of excellent transparency, affinity with (meth)acrylate, and closeness of refractive index.

[0046] When performing the unevenness transfer of the cured resin layer, in consideration of improving the scratch resistance and hardness, it is preferable to include a resin having an active energy ray curable functional group such as a carbon-carbon double bond. Examples of the active energy ray curable functional group include a (meth)acryloyl group and a vinyl ether compound. Among these, in consideration of the ease of introduction and reactivity, a (meth)acryloyl group, particularly an acryloyl group, is preferred.

[0047] In the course of further investigation, it was found that when the cured resin composition further contains a resin having an active energy ray-curable functional group, not only the properties directly related to the active energy ray-curable functional group, such as improved scratch resistance and hardness, but also an appropriate uneven shape can be formed on the surface of the cured resin layer. That is, it was found that the center-to-center distance (Rsm) between adjacent convex portions in the unevenness becomes smaller, and the arithmetic mean height (Sa), which is one of the indexes of surface roughness of the uneven structure, also becomes larger. In addition, there were also cases where the haze became higher and the gloss became lower. These properties can exert a synergistic effect on the matte property, and are important properties, especially in applications where visibility is important, such as display applications.

[0048] Examples of methods for introducing double bonds into acrylic resins having active energy ray-curable functional groups such as carbon-carbon double bonds include a method of reacting an acrylic resin having an epoxy group with a compound having a double bond and a carboxyl group (Method 1), a method of reacting an acrylic resin having a carboxyl group with a compound having a double bond and an epoxy group (Method 2), a method of reacting an acrylic resin having a hydroxyl group with a compound having a double bond and a carboxyl group (Method 3), a method of reacting an acrylic resin having a carboxyl group with a compound having a double bond and a hydroxyl group (Method 4), a method of reacting an acrylic resin having an isocyanate group with a compound having a double bond and a hydroxyl group (Method 5), and a method of reacting an acrylic resin having a hydroxyl group with a compound having a double bond and an isocyanate group (Method 6). These methods may also be used in combination. In the following, a radically polymerizable monomer having a carbon-carbon double bond may be referred to as a vinyl monomer.

[0049] In the above-mentioned method 1, examples of vinyl monomers having an epoxy group used to obtain an acrylic resin having an epoxy group include glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, and 3,4-epoxycyclohexylmethyl (meth)acrylate. Among these, glycidyl (meth)acrylate is preferred, and glycidyl methacrylate is particularly preferred, in consideration of particularly good reactivity and ease of use of the material. These may be used alone or in combination of two or more.

[0050] Examples of the compound having a double bond and a carboxyl group in Method 1 include (meth)acrylic acid, carboxyethyl (meth)acrylate, an adduct of glycerin di(meth)acrylate and succinic anhydride, an adduct of pentaerythritol tri(meth)acrylate and succinic anhydride, and an adduct of pentaerythritol tri(meth)acrylate and phthalic anhydride. Among these, (meth)acrylic acid or an adduct of pentaerythritol tri(meth)acrylate and succinic anhydride is preferred, (meth)acrylic acid is more preferred, and acrylic acid is even more preferred. The compound having a double bond and a carboxyl group may be used alone or in combination of two or more.

[0051] In the method 2, examples of the vinyl monomer having a carboxyl group used to obtain an acrylic resin having a carboxyl group include (meth)acrylic acid, carboxyethyl (meth)acrylate, and polybasic acid-modified (meth)acrylate. Among these, (meth)acrylic acid is preferred, and acrylic acid is more preferred. These may be used alone or in combination of two or more.

[0052] In the method 2, examples of the compound having a double bond and an epoxy group include glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, etc. Among these, glycidyl (meth)acrylate is preferred. These may be used alone or in combination of two or more.

[0053] In the method 3, examples of the vinyl monomer having a hydroxyl group used to obtain an acrylic resin having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0054] In the above method 3, as the compound having a double bond and a carboxyl group, the same compounds as those in the above method 1 can be used.

[0055] In the method 4, the acrylic resin having a carboxyl group may be the same as that in the method 2.

[0056] In the method 4, examples of the compound having a double bond and a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0057] In the method 5, examples of the vinyl monomer having an isocyanate group used to obtain an acrylic resin having an isocyanate group include isocyanate ethyl (meth)acrylate.

[0058] In the above method 5, as the compound having a double bond and a hydroxyl group, for example, the same compounds as those exemplified in the above method 4 can be used.

[0059] In the method 6, the acrylic resin having a hydroxyl group may be the same as the compound in the method 3.

[0060] In the method 6, examples of the compound having a double bond and an isocyanate group include isocyanate ethyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0061] Among the above methods, method 1 is preferred because the reaction is easy to control. In method 1, the double bond is introduced by a ring-opening addition reaction between the epoxy group of the acrylic resin having an epoxy group and the carboxyl group of the compound having a double bond and a carboxyl group.

[0062] In the method 1, the amount of the epoxy group-containing monomer in the epoxy group-containing acrylic resin is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 15% by weight or more of the total amount of monomers constituting the epoxy group-containing acrylic resin. There is no particular upper limit, but it is preferably 99.9% by weight or less, more preferably 80% by weight or less, even more preferably 70% by weight or less, particularly preferably 50% by weight or less, and most preferably 40% by weight or less. When the amount of the monomer having an epoxy group in the acrylic resin having an epoxy group is within this range, not only is the adhesion, scratch resistance, and hardness between the cured resin layer (cured resin film) and the substrate improved, but also an appropriate uneven shape tends to be formed, and a decrease in Rsm, an improvement in Sa, and in some cases an increase in haze and a decrease in gloss can be achieved.

[0063] In the method 1, the ratio of the double bond and the carboxyl group to the epoxy group of the acrylic resin having an epoxy group is preferably 10 to 150 mol%, more preferably 30 to 130 mol%, and further preferably 50 to 110 mol%. By using the compound having a double bond and a carboxyl group in the above range, the reaction can be carried out without excess or deficiency, and the amount of raw material residue can be reduced.

[0064] Furthermore, the acrylic resin such as the above-mentioned acrylic resin having an epoxy group may be a copolymer of (meth)acrylates other than those mentioned above or other vinyl monomers. The polymerization reaction of these raw materials is usually radical polymerization, and can be carried out under conventionally known conditions.

[0065] Monomers that can be used in combination as raw materials include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, methoxy(poly)ethylene glycol (meth)acrylate, methoxy(poly)propylene glycol (meth)acrylate, methoxy(poly)ethylene glycol (poly)propylene glycol (meth)acrylate, octoxy(poly)ethylene glycol (meth)acrylate, octoxy(poly)propylene glycol (meth)acrylate, )acrylate, octoxytetramethylene glycol (meth)acrylate, lauroxy(poly)ethylene glycol (meth)acrylate, stearoxy(poly)ethylene glycol (meth)acrylate, etc. (meth)acrylates; ethyl(meth)acrylamide, n-butyl(meth)acrylamide, i-butyl(meth)acrylamide, t-butyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, N-hydroxypropyl(meth)acrylamide, N,N-dihydroxyethyl(meth)acrylamide, etc. acrylamides; styrene, p-chlorostyrene, p-bromostyrene, etc. styrene monomers, etc. These may be used alone or in combination of two or more.

[0066] The acrylic resin can be produced by a radical polymerization reaction using the above-mentioned raw material vinyl monomers. The radical polymerization reaction is preferably carried out in an organic solvent in the presence of a radical polymerization initiator.

[0067] Examples of organic solvents used in radical polymerization include ketone-based solvents such as acetone and methyl ethyl ketone (MEK); alcohol-based solvents such as ethanol, methanol, isopropyl alcohol (IPA), and isobutanol; ether-based solvents such as ethylene glycol dimethyl ether and propylene glycol monomethyl ether; ester-based solvents such as ethyl acetate, propylene glycol monomethyl ether acetate, and 2-ethoxyethyl acetate; and aromatic hydrocarbon solvents such as toluene. These organic solvents may be used alone or in combination of two or more.

[0068] Examples of radical polymerization initiators used in radical polymerization include organic peroxides such as benzoyl peroxide and di-t-butyl peroxide; and azo compounds such as 2,2'-azobisbutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile). These radical polymerization initiators may be used alone or in combination of two or more. The radical polymerization initiator is preferably used in an amount of 0.01 to 5 parts by mass per 100 parts by mass of the total of the vinyl monomers as the raw material.

[0069] In the radical polymerization, a chain transfer agent can be used for the purpose of controlling the weight average molecular weight of the acrylic resin. Examples of the chain transfer agent include butanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, octadecanethiol, cyclohexyl mercaptan, thiophenol, octyl thioglycolate, octyl 2-mercaptopropionate, octyl 3-mercaptopropionate, 2-ethylhexyl mercaptopropionate, 2-ethylhexyl thioglycolate, butyl-3-mercaptopropionate, mercaptopropyltrimethoxysilane, methyl-3-mercaptopropionate, 2,2-(ethylenediaminetetraacetate), ... Examples of the thiol-based compounds include thiol compounds such as mercaptoacetate, ethanethiol, 4-methylbenzenethiol, octanoic acid 2-mercaptoethyl ester, 1,8-dimercapto-3,6-dioxaoctane, decane trithiol, dodecyl mercaptan, diphenyl sulfoxide, dibenzyl sulfide, 2,3-dimethylcapto-1-propanol, mercaptoethanol, thiosalicylic acid, thioglycerol, thioglycolic acid, 3-mercaptopropionic acid, thiomalic acid, mercaptoacetic acid, mercaptosuccinic acid, and 2-mercaptoethanesulfonic acid. These compounds may be used alone or in combination of two or more.

[0070] The amount of the chain transfer agent used is preferably 0.1 to 25 parts by mass, more preferably 0.5 to 20 parts by mass, and even more preferably 1.0 to 15 parts by mass, based on 100 parts by mass of the total of the vinyl monomers as the raw material.

[0071] The reaction time of the radical polymerization is preferably 1 to 20 hours, more preferably 3 to 12 hours, and the reaction temperature is preferably 40 to 120°C, more preferably 50 to 100°C.

[0072] In order to react the acrylic resin with a compound having a double bond and a carboxyl group, the compound having a double bond and a carboxyl group, etc. may be added to the acrylic resin obtained as described above, and the reaction may be carried out in the presence of one or more catalysts such as triphenylphosphine, tetrabutylammonium bromide, tetramethylammonium chloride, triethylamine, etc., usually at a temperature of 90 to 140°C, preferably 100 to 120°C, for usually about 3 to 9 hours. Here, the catalyst is preferably used in a ratio of about 0.5 to 3 parts by mass per 100 parts by mass of the total of the raw material (meth)acrylic acid ester polymer and the compound having a double bond and a carboxyl group, etc. This reaction may be carried out continuously after the acrylic resin is produced by polymerization reaction, or may be carried out by adding the compound having a double bond and a carboxyl group, etc. after once separating the acrylic resin from the reaction system.

[0073] The amount of double bonds in the acrylic resin is preferably in the range of 0.1 to 10 mmol / g, more preferably 0.2 to 7.0 mmol / g, further preferably 0.5 to 5.0 mmol / g, particularly preferably 0.8 to 4.0 mmol / g, and most preferably 1.0 to 3.0 mmol / g. When the amount of double bonds in the acrylic resin is within the range, the adhesion between the cured resin layer and the substrate, scratch resistance, and hardness are improved, and the uneven shape tends to be more precisely controlled, and a reduction in Rsm, an improvement in Sa, and in some cases an increase in haze and a decrease in gloss can be achieved. The amount of double bonds means the concentration of (meth)acryloyl groups in the acrylic resin, that is, the amount of (meth)acryloyl groups introduced.

[0074] The weight average molecular weight (Mw) of the resin should be appropriately selected according to the application of the cured resin layer composition, but is usually 5000 or more, preferably 7000 or more, more preferably 9000 or more, and usually 200000 or less, preferably 100000 or less, more preferably 70000 or less, and even more preferably 50000 or less. Within the above range, it is easy to form surface irregularities. The weight average molecular weight (Mw) of the resin can be determined as a converted value based on polystyrene standard using gel permeation chromatography (GPC). Specific measurement conditions are shown in the examples below.

[0075] When the curable resin composition contains the above-mentioned resin other than the active energy ray curable compound, the content of the resin is preferably 50 mass % or less, more preferably 40 mass % or less, and further preferably 30 mass % or less in the non-volatile content of the curable resin composition from the viewpoint of the appearance and adhesion of the cured film. If the content of the resin is too high, there is a concern that the hardness of the cured film will decrease.

[0076] In the laminated film of the present invention, the cured resin layer needs to satisfy a specific parameter for its surface roughness. The method for satisfying the specific parameter is not particularly limited, but for example, particles can be included in the cured resin layer. By including particles in the cured resin layer, the matte finish can be further improved. The particles are not particularly limited, and conventionally known particles can be used. Specific examples include inorganic particles such as silica, hollow silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, zirconium oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. The inorganic particles may be particles whose surfaces have been modified with a silane coupling agent having a reactive group such as a (meth)acryloyl group. The organic particles are preferably of a crosslinked type in order to maintain their shape, and crosslinked acrylic resin particles and crosslinked styrene resin particles are more preferred. Two or more kinds of these particles may be used in combination.

[0077] The average primary particle size of the particles is preferably in the range of 0.01 to 30 μm, more preferably 0.05 to 10 μm, further preferably 0.1 to 5 μm, and particularly preferably 0.5 to 3 μm. When the average primary particle size of the particles is in this range, the matte properties are excellently improved.

[0078] From the viewpoint of improving the matte property, the content of the particles in the cured resin layer is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less, and particularly preferably 20% by mass or less, based on the non-volatile content. The lower limit is not particularly limited, but is preferably 0.1% by mass or more, more preferably 1% by mass or more.

[0079] (Photopolymerization initiator) When the cured resin layer is formed using an active energy ray-curable compound, a photopolymerization initiator may be used. The molecular weight of the photopolymerization initiator is preferably 1,000 or less. Specific examples of photopolymerization initiators include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin-n-butyl ether, benzoin phenyl ether, benzyl diphenyl disulfide, dibenzyl, diacetyl, anthraquinone, naphthoquinone, 3,3'-dimethyl-4-methoxybenzophenone, benzophenone, p,p'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, pivaloyl ethyl ether, benzyl dimethyl ketal, 1,1-dichloroacetophenone, pt-butyl dichloroacetophenone, 2- ... Examples of suitable thioxanthone include thioxanthone, 2-methylthioxanthone, 2,4-diethylthioxanthone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-dichloro-4-phenoxyacetophenone, phenyl glyoxylate, α-hydroxyisobutylphenone, dibenzosuberone, 1-(4-isopropylphenyl)-2-hydroxy-2-methyl-1-propanone, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 1-hydroxycyclohexyl-phenyl ketone, tribromophenyl sulfone, and tribromomethylphenyl sulfone. These photopolymerization initiators may be used alone or in combination of two or more.

[0080] The content of the photopolymerization initiator in the curable resin composition is preferably 20 mass % or less, more preferably 10 mass % or less, even more preferably 8 mass % or less, and particularly preferably 6 mass % or less, of the non-volatile components of the curable resin composition, from the viewpoints of promoting curing and the hardness of the cured resin layer.

[0081] (Polymers having active groups that generate radicals upon irradiation with active energy rays) When forming a cured resin layer, a polymer having an active group that generates radicals by irradiation with active energy rays (hereinafter referred to as a polymer) may be used. The active group that generates radicals by irradiation with active energy rays (hereinafter referred to as an active group) is a group having a structure that generates radicals by irradiation with active energy rays, in other words, a structure that has photopolymerization initiation properties. Examples of the structure that has photopolymerization initiation properties include hydrogen abstraction type, electron transfer type, and intramolecular cleavage type. In the present invention, the radicals generated from the active group react with the polymer itself or an active energy ray-curable compound to form a crosslinked structure. (active group) Examples of active groups include benzophenone groups, acetophenone groups, benzoin groups, α-hydroxyketone groups (e.g., a group in which one hydrogen atom has been removed from the "hydroxyl group in 2-hydroxyethoxy" of 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-methylpropanone), α-aminoketone groups, α-diketone groups, α-diketone dialkyl acetal groups, anthraquinone groups, thioxanthone groups, and phosphine oxide groups. Among these, benzophenone groups, acetophenone groups, and α-hydroxyketone groups are preferred because they are less susceptible to oxygen inhibition during curing and provide good surface curing properties when forming a concave-convex layer.

[0082] The active group may be present at the terminal of the main chain of the polymer, or may be present in a constituent unit derived from a monomer that constitutes the polymer. It is preferable for the polymer to have multiple active groups in its molecule, since this allows for a higher concentration of active groups near the coating surface, makes the polymer less susceptible to oxygen inhibition and thus improves curability, and makes it easier for an uneven structure to appear on the cured surface.

[0083] As the polymer having a plurality of active groups, a polymer having a constitutional unit derived from a monomer (a) having an active group is preferable.

[0084] (Monomer (a)) The monomer (a) may be a compound having an active group and a radically polymerizable group. The radically polymerizable group may be a functional group containing a radically polymerizable unsaturated bond such as a carbon-carbon double bond. As the monomer (a), from the viewpoint of ease of synthesis of the polymer and ease of adjustment of the amount of the active group introduced, a (meth)acrylic acid ester is preferable. Examples of such a (meth)acrylic acid ester include 4-methacryloyloxybenzophenone and 2-[4-(2-hydroxy-2-methyl-1-oxopropyl)phenoxy]ethyl methacrylate.

[0085] The proportion of the constituent units derived from the monomer (a) relative to the total mass of all units constituting the polymer is preferably in the range of 1 to 90 mass%, more preferably 5 to 80 mass%, further preferably 15 to 70 mass%, and particularly preferably 30 to 60 mass%. If this proportion is within the above range, the curability can be improved and an uneven structure can be effectively formed.

[0086] (Monomer (b)) The polymer preferably has a structural unit derived from a monomer (b) having a chain structure in addition to a structural unit derived from a monomer (a) having an active group. The monomer (b) may be a compound having at least one chain structure selected from the group consisting of an alkyl group having 4 or more carbon atoms, a fluoroalkyl group, and a polydimethylsiloxane chain, and a radical polymerizable group. The radical polymerizable group may be a functional group containing a radical polymerizable unsaturated bond such as a carbon-carbon double bond. As the monomer (b), a (meth)acrylic acid ester is preferred from the viewpoint of ease of synthesis of the polymer and ease of adjustment of the amount of chain structure introduced. If the polymer has this unit, when a coating film of the curable composition is formed, the polymer is likely to segregate to the surface side of the coating film. Due to such segregation, the curing reaction inside the coating film (substrate film side) is less susceptible to oxygen inhibition, and the curability is improved. For example, it can be cured with a low exposure dose, and even a thin coating film that tends to be easily inhibited by oxygen can be cured well.

[0087] The alkyl group having 4 or more carbon atoms may be either linear or branched, and may contain a monocyclic or polycyclic ring structure. From the viewpoint of more effectively segregating the polymer on the surface of the coating film, the alkyl group is preferably linear. The carbon number of the alkyl group having 4 or more carbon atoms is preferably in the range of 4 to 30, more preferably in the range of 6 to 20, and even more preferably in the range of 8 to 18, from the viewpoint of more effectively segregating the polymer to the surface of the coating film.

[0088] Examples of monomers having an alkyl group having 4 or more carbon atoms include compounds having an alkyl group having 4 or more carbon atoms and a radical polymerizable group. Examples of such compounds include (meth)acrylic acid alkyl esters, fumaric acid dialkyl esters, maleic acid dialkyl esters, and aliphatic olefins. From the viewpoints of ease of synthesis and ease of adjusting the amount of the alkyl group having 4 or more carbon atoms introduced, (meth)acrylic acid alkyl esters are preferred.

[0089] Examples of such (meth)acrylic acid alkyl esters include butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and isodecyl (meth)acrylate. (meth)acrylate, dodecyl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, tridecyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, tricyclodecane (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, and the like. Among these, it is preferable to include a (meth)acrylic acid alkyl ester having a linear or branched alkyl group having 4 or more carbon atoms. As the (meth)acrylic acid alkyl ester having a linear or branched alkyl group having 4 or more carbon atoms, it is preferable that the number of carbon atoms in the alkyl group is within the above-mentioned preferred range, and taking into consideration ease of production, etc., 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate are more preferable, and 2-ethylhexyl (meth)acrylate and stearyl (meth)acrylate are particularly preferable. These (meth)acrylic acid alkyl esters may be used alone or in combination of two or more.

[0090] In order to more effectively segregate the polymer on the surface of the coating film, the polymer may have a structural unit derived from a monomer containing a fluoroalkyl group or a polydimethylsiloxane chain, in addition to or instead of the structural unit derived from a monomer having an alkyl group having 4 or more carbon atoms.

[0091] As the monomer containing a fluoroalkyl group, a (meth)acrylic acid ester containing a fluoroalkyl group is preferable, and a (meth)acrylic acid ester having a perfluoroalkyl group is more preferable. Examples of the (meth)acrylic acid ester having a perfluoroalkyl group include 2,2,2-trifluoroethyl acrylate (Viscoat 3F, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 2,2,3,3-tetrafluoropropyl acrylate (Viscoat 4F, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1H,1H,5H-octafluoropentyl acrylate (Viscoat 8F, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1H,1H,5H-octafluoropentyl methacrylate (Viscoat 8FM, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1H,1H,2H,2H-tridecafluorooctyl acrylate (Viscoat 13F, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1H,1H,2H,2H-nonafluorohexyl acrylate (CHEMINOX FAAC-4, manufactured by Unimatec Corporation), and 1H,1H,2H,2H-nonafluorohexyl methacrylate (CHEMINOX FAAC-4, manufactured by Unimatec Corporation). Commercially available examples include 1H,1H,2H,2H-tridecafluorooctyl methacrylate (Unimatec Co., Ltd., CHEMINOX FAMAC-6), and 2-(perfluorohexyl)ethyl methacrylate (Daikin Industries, Ltd., product name: C6SFMA monomer). The number of carbon atoms in the perfluoroalkyl group is preferably 3 or more.

[0092] The monomer containing a polydimethylsiloxane chain is preferably a (meth)acrylic acid ester containing a polydimethylsiloxane chain. A specific example of a (meth)acrylic acid ester having a polydimethylsiloxane chain is a polydimethylsiloxane having a molecular weight of 500 to 50,000 and substituted with a (meth)acryloyl group at one end. The molecular weight is preferably 1,000 to 30,000, more preferably 1,500 to 20,000. Examples of (meth)acrylic acid esters having a polydimethylsiloxane chain include "FM-0711", "FM-0721", and "FM-0725" (all manufactured by JNC Corporation), and "X-24-8201", "X-22-174DX", and "X-22-2426" (all manufactured by Shin-Etsu Chemical Co., Ltd.), which are commercially available.

[0093] The proportion of the monomer (b) relative to the total mass of all units constituting the polymer is preferably 80 mass% or less, more preferably 1 to 55 mass%, further preferably 5 to 50 mass%, and particularly preferably 8 to 40 mass%. If the proportion of the monomer (b) is within the above range, the curability can be improved and a concave-convex structure can be effectively formed.

[0094] (Monomers Having Hydrogen Donor Functional Groups) The polymer may have a structural unit derived from a monomer having a hydrogen donor functional group, if necessary. In particular, when the active group contains a hydrogen abstraction type, it is preferable to contain a structural unit derived from a monomer having a hydrogen donor functional group. If the polymer has this unit, the coating film of the curable composition is effectively cured from the surface, so that the curability is improved and the uneven structure is easily formed. Examples of the hydrogen donating functional group include a hydroxyl group, an amino group, a mercapto group, and an amide group. Among these, a hydroxyl group, an amino group, or an amide group is preferred from the viewpoint of the curing reaction proceeding particularly efficiently, improving the curability, or facilitating the formation of an uneven structure.

[0095] Examples of the monomer having a hydrogen donor functional group include a compound having a hydrogen donor functional group and a radical polymerizable group. From the viewpoints of ease of synthesis of the compound and ease of adjustment of the amount of hydrogen donor functional group to be introduced, a (meth)acrylic acid ester having a hydrogen donor functional group is preferred. Examples of monomers having a hydrogen donating functional group include hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, monobutyl hydroxyl fumarate, and monobutyl hydroxy itaconate; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-vinyl caprolactam, N-vinyl pyrrolidone, and N-isopropyl (meth)acrylamide. Examples of the monomers include amino group- or amide group-containing monomers such as N,N-dimethylaminoethyl (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, 2-[(butylamino)carbonyl]oxy]ethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-diethylaminopropyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylamide, (meth)acryloylmorpholine, and vinylacetamide. Among these, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, N,N-dimethylacrylamide, N,N-dimethylaminoethyl (meth)acrylate, and N,N-diethylaminoethyl (meth)acrylate are preferred because they have an excellent curing acceleration effect when used in combination with an active group, and N,N-diethylaminoethyl (meth)acrylate is more preferred because it is easy to enlarge the uneven structure. These compounds may be used alone or in combination of two or more.

[0096] (Other monomers) The polymer may further contain, as necessary, a structural unit derived from a monomer other than the above. Examples of the other monomer include a compound having a radical polymerizable group but not having an active group, an alkyl group having 4 or more carbon atoms, a fluorine atom, a silicon atom, or a hydrogen donor functional group. Examples of other monomers include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate; glycidyl (meth)acrylate and (meth)acryloyloxybenzophenone; nitrogen-containing monomers such as (meth)acrylonitrile; styrene-based compounds such as styrene, α-methylstyrene, divinylbenzene, and vinyltoluene; vinyl esters such as vinyl propionate and vinyl acetate; silicon-containing monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; vinyl halides such as vinyl chloride and vinylidene chloride; and conjugated dienes such as butadiene.

[0097] The proportion of the structural units derived from the monomer having a hydrogen donor functional group relative to the total mass of all units constituting the polymer is preferably 80 mass% or less, more preferably 1 to 40 mass%, further preferably 3 to 35 mass%, and particularly preferably 5 to 34 mass%. If this proportion is within the above range, the curability can be improved and an uneven structure can be effectively formed.

[0098] (Weight average molecular weight) The weight average molecular weight (Mw) of the polymer is preferably in the range of 1,000 to 500,000, more preferably 3,000 to 300,000, further preferably 5,000 to 200,000, and particularly preferably 10,000 to 150,000. When Mw is within the above range, the coatability and curability of the curable composition tend to be further improved, and the ease of forming an uneven structure tends to be further improved. The Mw of the polymer is a value calculated in terms of standard polystyrene as measured by gel permeation chromatography (GPC). Detailed measurement conditions are as described in the Examples below.

[0099] The content of the active group per 1 g of the polymer is preferably in the range of 0.1 to 3.5 mmol / g, more preferably 0.3 to 3.0 mmol / g, further preferably 0.5 to 2.7 mmol / g, and particularly preferably 1.0 to 2.5 mmol / g. When the content of the active group is within the above range, the curability is excellent and the unevenness can be formed more effectively.

[0100] (glass transition temperature) The glass transition temperature (Tg) of the polymer is preferably in the range of −30 to 150° C., more preferably 0 to 120° C., and further preferably 25 to 100° C. When the Tg of the polymer is within the above range, the curability tends to be further improved, and the ease of forming a concave-convex structure tends to be further improved.

[0101] (Polymer production) Typically, the polymer can be produced by polymerizing the raw material monomer in the presence of a polymerization initiator. During polymerization, a chain transfer agent may be used in combination, if necessary. Examples of the polymerization method include solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization, and among these, solution polymerization is preferred in terms of its simple operation and high productivity.

[0102] (Polymer content) The polymer content in the non-volatile matter of the curable composition of the present invention is preferably from 0.5 to 25.0 mass%, more preferably from 0.7 to 20.0 mass%, even more preferably from 1.0 to 15.0 mass%, particularly preferably from 2.0 to 12.0 mass%, and most preferably from 3.0 to 12.0 mass%, in terms of imparting an uneven structure to the surface of the cured product and achieving good active energy ray curability. The non-volatile content of the curable composition is the total mass of components other than the solvent such as the organic solvent. The proportion of the non-volatile content in the curable composition can be measured by a conventionally known method, and can be calculated from the change in weight when, for example, 1 g of the composition is spread and heated at 100° C. for 1 hour to volatilize the organic solvent.

[0103] From the viewpoint of improving the appearance of the cured resin layer, the cured resin composition may contain a leveling agent. Examples of the leveling agent include acrylic leveling agents, silicone leveling agents, fluorine-based leveling agents, etc. These leveling agents may be used alone or in combination of two or more kinds.

[0104] The content of the leveling agent in the cured resin composition is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less, based on the non-volatile content, from the viewpoint of improving the appearance of the cured film.

[0105] The cured resin layer may contain a polymerization accelerator such as a compound containing a thiol group, a plasticizer, a surfactant, an antioxidant, an ultraviolet absorber, etc., within the scope of not impairing the effects of the present invention.

[0106] (Organic solvent) The cured resin layer can be formed, for example, by applying the curable resin composition onto the substrate film. In this case, an organic solvent may be used as necessary to improve workability when applying the curable resin composition onto the substrate film. Examples of organic solvents include aromatic solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone, acetone, methyl isobutyl ketone, and cyclohexanone; ether solvents such as diethyl ether, isopropyl ether, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, anisole, and phenetole; ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, and ethylene glycol diacetate; amide solvents such as dimethylformamide, diethylformamide, and N-methylpyrrolidone; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, and butyl cellosolve; alcohol solvents such as methanol, ethanol, propanol, isopropanol, and butanol; and halogen-based solvents such as dichloromethane and chloroform. Among these, ester solvents, ether solvents, alcohol solvents, and ketone solvents are preferred in that they are easy to improve the workability in coating. These organic solvents may be used alone or in combination of two or more.

[0107] The ratio of the organic solvent to 100 parts by mass of the nonvolatile content of the cured resin layer composition is preferably from 10 to 1,900 parts by mass, more preferably from 40 to 400 parts by mass, from the viewpoint of improving workability. The non-volatile content of the cured resin layer composition is the total mass of components other than the solvent such as the organic solvent. The non-volatile content of the cured resin layer composition can be measured by a conventionally known method, for example, by measuring the change in weight when 1 g of the composition is spread and heated at 100° C. for 1 hour to volatilize the organic solvent.

[0108] (Method of forming a cured resin layer) The cured resin layer can be formed by applying the cured resin layer composition onto a substrate film to form a coating film, optionally drying the coating film, and then irradiating the coating film with active energy rays. The method for applying the cured resin layer composition is not particularly limited, and can be a known method such as dip coating, air knife coating, curtain coating, spin coating, roller coating, bar coating, wire bar coating, gravure coating, or spray coating.

[0109] When the cured resin layer composition contains an organic solvent, it is preferable to heat-dry the composition before irradiation with active energy rays. By heating and drying the composition beforehand, the solvent in the coating film can be effectively removed. The drying temperature for the heat drying is preferably from 30° C. to 200° C., more preferably from 40° C. to 150° C. The drying time is preferably from 0.01 to 30 minutes, more preferably from 0.1 to 10 minutes.

[0110] (Irradiation with active energy rays) The active energy ray may be at least one selected from the group consisting of ultraviolet rays, vacuum ultraviolet rays, electron beams, and ionizing radiation, from the viewpoint of effectively curing the surface of the coating film. In one aspect of the method for forming a cured resin layer of the present invention, it is preferable to include a step of forming the cured resin layer by excimer lamp irradiation or ultraviolet (UV) irradiation.

[0111] Ultraviolet rays refer to active energy rays whose radiation spectrum has a maximum value between 200 nm and 600 nm. For example, ultraviolet ray emitting lamps include high pressure mercury lamps, medium pressure mercury lamps, low pressure mercury lamps, ultra-high pressure mercury lamps, metal halide lamps, LEDs, xenon flash lamps, and electrodeless lamps.

[0112] The cumulative amount of ultraviolet light to be irradiated is preferably 1 to 5000 mJ / cm 2 , more preferably 50 to 3000 mJ / cm 2 , and more preferably 100 to 1000 mJ / cm 2 , particularly preferably 200 to 700 mJ / cm 2 The illuminance is preferably in the range of 1 to 1000 mW / cm 2 , more preferably 50 to 500 mW / cm 2, and more preferably 80 to 300 mW / cm 2 The range is.

[0113] For vacuum ultraviolet rays (ultraviolet rays with a wavelength of 200 nm or less), excimer light with a half-width of 50 nm or less is optimal, and examples of such light include argon (126 nm), krypton (146 nm), xenon (172 nm), and argon-fluorine (193 nm). Among these, xenon excimer light is most suitable, taking into consideration ease of use, effective formation of unevenness, and the curing properties of the cured resin layer.

[0114] When using vacuum ultraviolet light, the integrated light amount of irradiation is preferably 1 to 3000 mJ / cm 2 , more preferably 3 to 1000 mJ / cm 2 , and more preferably 5 to 500 mJ / cm 2 , particularly preferably 10 to 100 mJ / cm 2 The illuminance is preferably in the range of 1 to 500 mW / cm 2 , more preferably 2 to 300 mW / cm 2 , and more preferably 3 to 100 mW / cm 2 The range is.

[0115] The vacuum ultraviolet irradiation is preferably performed in an environment with low oxygen such as a nitrogen atmosphere, etc. The oxygen concentration is preferably 10% or less, more preferably 5% or less, further preferably 3% or less, and particularly preferably 1% or less.

[0116] After the above-mentioned vacuum ultraviolet irradiation, in order to cure the cured resin layer to a deep portion, it is preferable to irradiate it with an active energy ray other than vacuum ultraviolet rays. Examples of the active energy ray other than vacuum ultraviolet rays include ultraviolet rays and electron beams, and among these, ultraviolet rays are more preferable in consideration of the curability of the cured film.

[0117] (Thickness of cured resin layer) The thickness of the cured resin layer is preferably in the range of 1 to 100 μm, more preferably 2 to 80 μm, further preferably 3 to 50 μm, and particularly preferably 3 to 30 μm. When the thickness of the cured resin layer is within the above range, it is easy to achieve the desired matte property and to adjust the hardness. In one embodiment of the present invention, a transfer product is provided to which the uneven structure of the cured resin layer surface is transferred. In this case, the thickness of the transfer product obtained by the uneven transfer of the cured resin layer indicates the maximum thickness of the uneven layer, and is determined by cross-sectional observation using an electron microscope.

[0118] [Release layer] The laminate film of the present invention may have a release layer on the cured resin layer. Hereinafter, an embodiment in which the laminate film of the present invention is a release film having a release layer on a cured resin layer will be described. The role of the release layer is not only to protect various objects to be protected and to prevent contamination of the protective film, but also to contribute to improving the handling properties of the laminate film of the present invention. For example, when the laminate film of the present invention is stacked in sheets or wound in a roll, the release layer has the effects of preventing the laminate film from sticking to the adhesive layer on the back side thereof and facilitating peeling, as well as improving the slipperiness to facilitate the production of the laminate film, improving the handling properties of the laminate film, and improving the processability of the adhesive layer on the laminate film. The thickness of the release layer is not particularly limited as long as it is within a range in which the effects of the present invention can be obtained, but is preferably in the range of 0.001 to 5 μm, more preferably 0.01 to 3 μm, and even more preferably 0.1 to 2 μm. By setting the thickness of the release layer within the above range, it is possible to improve the appearance, water repellency, and release property (anti-sticking property with the adhesive layer). In one embodiment of the present invention, a transfer product is also provided to which the unevenness of the release layer surface of the release film is transferred. In this case, the thickness of the transfer product obtained by transferring the unevenness of the release layer surface indicates the maximum thickness of the uneven layer, and is determined by cross-sectional observation using an electron microscope.

[0119] <Release agent> The release agent for forming the release layer is not particularly limited, and any conventionally known release agent can be used. For example, at least one selected from the group consisting of long-chain alkyl group-containing compounds, melamine compounds, fluorine compounds, silicone compounds, and waxes can be used. Among these, long-chain alkyl compounds and fluorine compounds are preferred because they are less likely to stain the surface of the object to be protected and have excellent water repellency, or silicone compounds are preferred because they provide good releasability to the adhesive layer. These release agents may be used alone or in combination of two or more kinds.

[0120] (Long-chain alkyl group-containing compounds) The long-chain alkyl group-containing compound is a compound having a linear or branched alkyl group having a carbon number of usually 6 or more, preferably 8 or more, and more preferably 12 or more. The upper limit of the carbon number is not particularly limited, but is, for example, 30. Examples of the alkyl group include a hexyl group, an octyl group, a decyl group, a lauryl group, an octadecyl group, and a behenyl group. Examples of compounds having an alkyl group include various long-chain alkyl group-containing polymer compounds, long-chain alkyl group-containing amine compounds, long-chain alkyl group-containing ether compounds, and long-chain alkyl group-containing quaternary ammonium salts. Considering heat resistance and stain resistance, it is preferable to use a long-chain alkyl group-containing polymer compound. In addition, from the viewpoint of effectively obtaining releasability, it is more preferable to use a polymer compound having a long-chain alkyl group in the side chain.

[0121] The polymer compound having a long-chain alkyl group in the side chain can be obtained by reacting a polymer having a reactive group with a compound having an alkyl group capable of reacting with the reactive group. Examples of the reactive group include hydroxyl group, amino group, carboxyl group, acid anhydride, etc. Examples of the compound having these reactive groups include polyvinyl alcohol, polyethyleneimine, polyethyleneamine, reactive group-containing polyester resin, reactive group-containing poly(meth)acrylic resin, etc. Among these, polyvinyl alcohol is preferable in consideration of releasability and ease of handling.

[0122] Examples of compounds having an alkyl group capable of reacting with the reactive group include long-chain alkyl group-containing isocyanates such as hexyl isocyanate, octyl isocyanate, decyl isocyanate, lauryl isocyanate, octadecyl isocyanate, behenyl isocyanate, etc., long-chain alkyl group-containing chlorides such as hexyl chloride, octyl chloride, decyl chloride, lauryl chloride, octadecyl chloride, behenyl chloride, etc., long-chain alkyl group-containing amines, long-chain alkyl group-containing alcohols, etc. Among these, in consideration of releasability and ease of handling, long-chain alkyl group-containing isocyanates are preferred, and octadecyl isocyanate is particularly preferred.

[0123] The polymeric compound having a long-chain alkyl group in the side chain may be a polymer of a long-chain alkyl (meth)acrylate or a copolymer of a long-chain alkyl (meth)acrylate and another vinyl group-containing monomer. Examples of the long-chain alkyl (meth)acrylate include hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, and behenyl (meth)acrylate.

[0124] (Fluorine compounds) The fluorine compound is not particularly limited as long as it contains fluorine atoms in the compound. From the viewpoint of the coating appearance by in-line coating, organic fluorine compounds are preferably used, for example, perfluoroalkyl group-containing compounds, polymers of olefin compounds containing fluorine atoms, aromatic fluorine compounds such as fluorobenzene, etc. From the viewpoint of mold releasability, it is preferable to use a compound having a perfluoroalkyl group. Furthermore, as the fluorine compound, compounds containing long chain alkyl compounds as described later can also be used.

[0125] Examples of compounds having a perfluoroalkyl group include perfluoroalkyl group-containing (meth)acrylates such as perfluoroalkyl(meth)acrylate, perfluoroalkylmethyl(meth)acrylate, 2-perfluoroalkylethyl(meth)acrylate, 3-perfluoroalkylpropyl(meth)acrylate, 3-perfluoroalkyl-1-methylpropyl(meth)acrylate, 3-perfluoroalkyl-2-propenyl(meth)acrylate, and polymers thereof; perfluoroalkyl group-containing vinyl ethers such as perfluoroalkylmethylvinyl ether, 2-perfluoroalkylethylvinyl ether, 3-perfluoropropylvinyl ether, 3-perfluoroalkyl-1-methylpropylvinyl ether, 3-perfluoroalkyl-2-propenylvinyl ether, and polymers thereof. Among the above, a polymer is preferable in consideration of heat resistance and stain resistance. The polymer may be a polymer of a single compound or a polymer of multiple compounds. From the viewpoint of releasability, the perfluoroalkyl group preferably has 3 to 11 carbon atoms. Furthermore, as described later, it may be a polymer with a compound containing a long-chain alkyl compound. From the viewpoint of adhesion to a substrate, a polymer with vinyl chloride is also preferable.

[0126] (Silicone compounds) Silicone compounds are compounds having a silicone structure in the molecule. Examples include alkyl silicones such as dimethyl silicone and diethyl silicone, phenyl silicones having a phenyl group, and methylphenyl silicones. Silicone compounds having various functional groups in the silicone structure can also be used, such as silicone compounds having a polyether group, a hydroxyl group, an amino group, an epoxy group, a carboxylic acid group, a halogen group such as fluorine, a perfluoroalkyl group, various alkyl groups, and various aromatic groups, etc. in the silicone structure. Silicones having a vinyl group and hydrogen silicones in which hydrogen atoms are directly bonded to silicon atoms are also common, and it is also possible to use both together to use an addition type silicone (a type obtained by the addition reaction of a vinyl group and a hydrogen silane).

[0127] In addition, modified silicones such as acrylic-grafted silicone, silicone-grafted acrylic, amino-modified silicone, and perfluoroalkyl-modified silicone can also be used as the silicone compound. In consideration of heat resistance and stain resistance, it is preferable to use a curable silicone resin, and any curing reaction type such as an addition type or an active energy ray curable type can be used. The curable silicone resin will be described in detail later.

[0128] <Polyether group-containing silicone compound> As the silicone compound, polyether group-containing silicone compound is preferred from the viewpoint of low backside transfer, good dispersibility in aqueous solvent, and high suitability for in-line coating.Position of polyether group in silicone structure is not particularly limited, and polyether group may be present in side chain or terminal of silicone, or polyether group may be present in main chain.From the viewpoint of dispersibility in aqueous solvent, it is preferred to have polyether group in side chain or terminal.

[0129] The polyether group may have a structure that is publicly known in the art. From the viewpoint of dispersibility in aqueous solvents, aliphatic polyether groups are preferred over aromatic polyether groups, and among aliphatic polyether groups, alkyl polyether groups are preferred. From the viewpoint of synthesis due to steric hindrance, linear alkyl polyether groups are preferred over branched alkyl polyether groups, and among them, polyether groups consisting of linear alkyl having 8 or less carbon atoms are preferred. Furthermore, when the solvent is water, taking into consideration dispersibility in water, polyethylene glycol groups or polypropylene glycol groups are preferred, and polyethylene glycol groups are particularly optimal.

[0130] From the viewpoint of improving dispersibility in aqueous solvents and durability of the release layer, the number of ether bonds in the polyether group is usually in the range of 1 to 30, preferably in the range of 2 to 20, and more preferably in the range of 3 to 15. When the number of ether bonds is equal to or more than the above lower limit, sufficient dispersibility can be ensured, and when it is equal to or less than the above upper limit, durability and release performance are not adversely affected.

[0131] When the silicone structure has a polyether group at its side chain or end, the end of the polyether group is not particularly limited, and various functional groups can be used, such as a hydroxyl group, an amino group, a thiol group, a hydrocarbon group such as an alkyl group or a phenyl group, a carboxylic acid group, a sulfonic acid group, an aldehyde group, an acetal group, etc. Among them, in consideration of dispersibility in water and crosslinking properties for improving the strength of the release layer, at least one selected from the group consisting of a hydroxyl group, an amino group, a carboxylic acid group, and a sulfonic acid group is preferred, and a hydroxyl group is particularly optimal.

[0132] The content of the polyether group in the polyether group-containing silicone compound is preferably in the range of 0.001 to 0.30, more preferably in the range of 0.01 to 0.20, further preferably in the range of 0.03 to 0.15, and particularly preferably in the range of 0.05 to 0.12, in terms of molar ratio, with the siloxane bond of silicone being 1. By keeping the content within this range, it is possible to maintain dispersibility in water, durability of the release layer, and good releasability.

[0133] The molecular weight of the polyether group-containing silicone compound is preferably not too large in consideration of dispersibility in an aqueous solvent, and is preferably somewhat large in consideration of the durability and release performance of the release layer. It is required to balance these two properties, and the number average molecular weight is preferably in the range of 1,000 to 100,000, more preferably in the range of 3,000 to 30,000, and even more preferably in the range of 5,000 to 10,000.

[0134] Considering the changes over time and release performance of the release layer, as well as contamination in various processes, it is preferable that the low molecular weight components (number average molecular weight of 500 or less) of the silicone compound be as small as possible, and the amount thereof, as a proportion of the total silicone compound, is preferably 15 mass % or less, more preferably 10 mass % or less, and even more preferably 5 mass % or less. In addition, when condensation type silicone is used as the silicone compound, if the vinyl group (vinyl silane) or hydrogen group (hydrogen silane) bonded to silicon remains unreacted in the release layer, it will cause various performances to change over time. Therefore, as the amount of functional groups in the silicone, the content of the unreacted functional groups is preferably 0.1 mol% or less, and more preferably, it is not contained.

[0135] <Surfactant> Polyether group-containing silicone is difficult to apply by itself, so it is preferable to use it by dispersing it in water.For dispersion, various conventionally known surfactants can be used.For example, anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants can be mentioned. Among these, when taking into consideration the dispersibility of the polyether group-containing silicone and the compatibility with polymers other than the polyether group-containing silicone that may be used in forming the release layer, anionic surfactants and nonionic surfactants are preferred. In place of these surfactants, fluorine compounds can also be used.

[0136] Examples of the anionic surfactant include sulfonate-based and sulfate-based surfactants such as sodium dodecylbenzenesulfonate, sodium alkylsulfonate, sodium alkylnaphthalenesulfonate, sodium dialkylsulfosuccinate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl allyl ether sulfate, and polyoxyalkylene alkenyl ether ammonium sulfate; carboxylate-based surfactants such as sodium laurate and potassium oleate; and phosphate-based surfactants such as alkyl phosphates, polyoxyethylene alkyl ether phosphates, and polyoxyethylene alkyl phenyl ether phosphates. Among these, the sulfonate type is preferred from the viewpoint of good dispersibility.

[0137] Examples of nonionic surfactants include ether types in which alkylene oxides such as ethylene oxide or propylene oxide are added to compounds having hydroxyl groups, such as higher alcohols or alkylphenols; ester types in which polyhydric alcohols such as glycerin or sugars are ester-bonded to fatty acids; ester-ether types in which alkylene oxides are added to fatty acids or polyhydric alcohol fatty acid esters; and amide types in which hydrophobic and hydrophilic groups are connected via amide bonds. Among these, the ether type is preferred in consideration of solubility in water and stability, and the ether type to which ethylene oxide is added is more preferred in consideration of handling properties.

[0138] Although it is difficult to generalize because it depends on the molecular weight and structure of the polyether group-containing silicone compound used, and also on the type of surfactant used, as a guideline, the amount of surfactant is preferably in the range of 0.01 to 0.5, more preferably 0.05 to 0.4, and even more preferably 0.1 to 0.3, in terms of mass ratio, assuming the amount of polyether group-containing silicone compound to be 1.

[0139] <Curing silicone resin> When using a silicone compound as the release agent constituting the release layer, as described above, a curable silicone resin can be used. The curable silicone resin may be a resin mainly composed of a curable silicone resin, or may be a modified silicone obtained by graft polymerization of a curable silicone resin with an organic resin such as a urethane resin, an epoxy resin, or an alkyd resin. In addition, when the adhesive layer is a silicone adhesive, it is preferable to contain a fluorosilicone resin or the like.

[0140] As the type of curable silicone resin, any of the existing curing reaction types can be used, such as heat curable types such as addition types and condensation types, electron beam curable types such as ultraviolet curable types, etc. The curable silicone resin may be used alone or in combination with a plurality of types. Furthermore, the form of the curable silicone resin to be applied when forming the release layer is not particularly limited, and it may be in the form of a solution in an organic solvent, in the form of a water-based emulsion, or in the form of a solventless solution. In the case of a water-based emulsion, it is preferable to use a surfactant. The surfactant may be the same as that used in the polyether group-containing silicone compound. Among them, anionic surfactants and nonionic surfactants are preferred from the viewpoint of dispersibility of the curable silicone resin.

[0141] Although there is no limitation on the type of curable silicone resin used in the present invention, it is preferable to use a curable silicone resin containing an alkenyl group in the present invention from the viewpoint of excellent release properties such as light peelability. As the curable silicone resin containing an alkenyl group, a diorganopolysiloxane represented by the following general formula (1) can be exemplified. R (3-a) X a SiO-(RXSiO) m -(R2SiO) n -SiX a R (3-a) (1)

[0142] In the general formula (1), R is a monovalent hydrocarbon group having 1 to 10 carbon atoms, and X is an organic group containing an alkenyl group. a is an integer of 0 to 3, preferably 1, and m is 0 or more, but when a=0, m is 2 or more. m and n are numbers that satisfy 100≦m+n≦20000. Note that the above formula does not mean a block copolymer. R is a monovalent hydrocarbon group having 1 to 10 carbon atoms. Specific examples include alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclohexyl; and aryl groups such as phenyl and tolyl. Of these, methyl and phenyl groups are particularly preferred. X is an alkenyl-containing organic group, preferably having 2 to 10 carbon atoms. Specific examples include a vinyl group, an allyl group, a hexenyl group, an octenyl group, an acryloylpropyl group, an acryloylmethyl group, a methacryloylpropyl group, a cyclohexenylethyl group, and a vinyloxypropyl group. In particular, a vinyl group, a hexenyl group, and the like are preferred. Specific examples of curable silicone resins containing alkenyl groups include dimethylsiloxane-methylhexenylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups (96 mol% dimethylsiloxane units, 4 mol% methylhexenylsiloxane units), dimethylsiloxane-methylhexenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups (97 mol% dimethylsiloxane units, 3 mol% methylhexenylsiloxane units), and dimethylsiloxane-methylhexenylsiloxane copolymers capped at both molecular chain terminals with dimethylhexenylsiloxy groups (95 mol% dimethylsiloxane units, 5 mol% methylhexenylsiloxane units). The number average molecular weight of the curable silicone resin is preferably 50,000 or more, more preferably 80,000 or more, even more preferably 100,000 or more, and particularly preferably 150,000 or more. On the other hand, the number average molecular weight is preferably 600,000 or less, more preferably 500,000 or less, and even more preferably 400,000 or less.

[0143] The release layer is preferably a layer formed by curing a silicone resin composition containing the above-mentioned curable silicone resin and a curing agent for curing the curable silicone resin. The curing agent may be polyorganosiloxane containing a SiH group. The polyorganosiloxane containing SiH group reacts with the curable silicone resin containing alkenyl group to form a stronger silicone release layer.As the polyorganosiloxane containing SiH group, an organohydrogenpolysiloxane having at least two, preferably three or more hydrogen atoms bonded to silicon atoms in one molecule, and linear, branched, cyclic, etc. can be used, and examples thereof include the compound represented by the following general formula (2), but are not limited thereto. H b R 1 (3-b) SiO-(HR 1 SiO) x -(R 1 2SiO) y -SiR 1 (3-b) H b (2)

[0144] In the general formula (2), R 1 is a monovalent hydrocarbon group having 1 to 6 carbon atoms containing no aliphatic unsaturated bonds, b is an integer of 0 to 3, and x and y are each an integer. Specific examples include methylhydrogenpolysiloxane capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer capped at both molecular chain terminals with trimethylsiloxy groups, methylhydrogenpolysiloxane capped at both molecular chain terminals with dimethylhydrogensiloxy groups, and dimethylsiloxane-methylhydrogensiloxane copolymer capped at both molecular chain terminals with dimethylhydrogensiloxy groups. In the silicone resin composition, the molar ratio of Si-H groups to alkenyl groups (Si-H groups / alkenyl groups) is preferably from 0.1 to 2.0, more preferably from 0.3 to 2.0, and even more preferably from 0.3 to 1.8.

[0145] Specific examples of commercially available silicone resins that can be used in the present invention include KS-774, KS-775, KS-778, KS-779H, KS-847H, KS-856, X-62-2422, X-62-2461, X-62-1387, X-62-5039, X-62-5040, KNS-3051, X-62-1496, KNS320A, KNS316, X-62-1574A / B, X-62-7052, X-62-7028A / B, X-62-7619, X-62-7213, and X-41-3035 manufactured by Shin-Etsu Chemical Co., Ltd.; and YSR-3022, TPR-6700, and TPR-6 manufactured by Momentive Performance Materials. 720, TPR-6721, TPR6500, TPR6501, UV9300, UV9425, XS56-A2775, XS56-A2982, UV9430, TPR6600, TPR6604, TPR6605, Toray Dow Corning Co., Ltd. SRX357, SRX211, SD7220, SD7292, LTC750A, Examples include LTC760A, LTC303E, LTC856, LTC761, SP7259, BY24-468C, SP7248S, BY24-452, DKQ3-202, DKQ3-203, DKQ3-204, DKQ3-205, DKQ3-210, and of the DEHESIVE series manufactured by Wacker Asahi Kasei Silicones Co., Ltd., DEHESIVE 636, 919, 920, 921, 924, 929, etc.

[0146] The release layer preferably contains a platinum-based catalyst that promotes an addition reaction, and therefore, the silicone resin composition preferably further contains a platinum-based catalyst. Examples of platinum-based catalysts include platinum-based compounds such as chloroplatinic acid, an alcohol solution of chloroplatinic acid, a complex of chloroplatinic acid with an olefin, and a complex of chloroplatinic acid with an alkenylsiloxane, platinum black, platinum supported on silica, and platinum supported on activated carbon. The content of the platinum-based catalyst in the release layer is not particularly limited, but is, for example, in the range of 0.01 to 10.0% by mass, preferably 0.01 to 5.0% by mass. When the content of the platinum-based catalyst in the release layer is 0.01% by mass or more, sufficient release force is obtained, the curing reaction proceeds sufficiently, and there is no problem such as deterioration of the surface condition, etc. On the other hand, when the content of the platinum-based catalyst in the release layer is 10.0% by mass or less, in addition to being advantageous in terms of cost, there is no process problem such as increased reactivity and generation of gel foreign matter.

[0147] Since the addition type silicone compound is very reactive, acetylene alcohol may be added as a reaction inhibitor in some cases. The reaction inhibitor can be exemplified by an organic compound having a carbon-carbon triple bond and a hydroxyl group, and is preferably at least one compound selected from the group consisting of 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol and phenylbutynol.

[0148] In order to adjust the release properties of the release layer, various release control agents may be used in combination. When the release force is to be made stronger, the release force can generally be adjusted by adding an appropriate content of organopolysiloxane resin, silica particles, heavy release type silicone species, etc. to the release layer to obtain the desired release force. Specific examples of commercially available heavy release agents include KS-3800 and X-92-183 manufactured by Shin-Etsu Chemical Co., Ltd., and SDY7292, BY24-843, and BY24-4980 manufactured by Dow Corning Toray Co., Ltd. When the release force is to be lightened, various low molecular weight siloxane compounds are selected and the content in the release layer is appropriately adjusted so that the siloxane migrating component exerts release performance. Examples of low molecular weight siloxane compounds include low molecular weight cyclic siloxanes such as hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane. Examples of other compounds of the low molecular weight cyclic siloxane include dimethylsiloxane oligomers with both molecular chain terminals blocked by trimethylsiloxy groups; dimethylsiloxane oligomers with both molecular chain terminals blocked by dimethylhydroxysiloxy groups, etc. These low molecular weight siloxane compounds may be mixed and used as necessary. These low molecular weight siloxane compounds are usually contained in the silicone resin as migratory components in an amount of 0.1 to 15.0% by mass, preferably 0.1 to 10.0% by mass, and more preferably 0.1 to 5% by mass, to achieve the desired light release. When the content of the low molecular weight siloxane compound is 0.1% by mass or more, the migratory components are sufficient, and sufficient releasability is exhibited. On the other hand, when the content of the low molecular weight siloxane compound is 15.0% by mass or less, the migratory components do not precipitate excessively, and there is no problem of process contamination.

[0149] In order to improve the coating adhesion to the laminated film of the present invention, it is preferable to use an organosilicon compound represented by the following general formula (3) in the release layer. Si(X) d (Y) e (R 1 ) f (3) [In the above formula, X is an organic group having at least one selected from the group consisting of an epoxy group, a mercapto group, a (meth)acryloyl group, an alkenyl group, a haloalkyl group, and an amino group, and a plurality of Xs may be the same or different; R 1 is a monovalent hydrocarbon group having 1 to 10 carbon atoms, Y is a hydrolyzable group, multiple Ys may be the same or different, d is an integer of 1 or 2, e is an integer of 2 or 3, f is an integer of 0 or 1, and d+e+f=4.

[0150] The organosilicon compound represented by the general formula (3) may be one having two hydrolyzable groups Y (D unit source) or three hydrolyzable groups Y (T unit source) that can form a siloxane bond by hydrolysis and condensation reaction.

[0151] In the general formula (3), a monovalent hydrocarbon group R having 1 to 10 carbon atoms 1 is particularly preferably a methyl group, an ethyl group, or a propyl group.

[0152] In the general formula (3), examples of the hydrolyzable group Y include the following: methoxy group, ethoxy group, butoxy group, isopropenoxy group, acetoxy group, butanoxime group, and amino group. These hydrolyzable groups may be used alone or in combination. Among them, methoxy group or ethoxy group is particularly preferred because it can impart good storage stability to the coating material and has appropriate hydrolysis.

[0153] Specific examples of organosilicon compounds contained in the release layer include vinyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 5-hexenyltrimethoxysilane, p-styryltrimethoxysilane, trifluoropropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldiisopropenoxysilane, and the like.

[0154] The content of the organosilicon compound in the release layer is preferably 0.5-5.0 parts by mass, more preferably 0.5-2.0 parts by mass, based on 100 parts by mass of the curable silicone resin. When the content of the organosilicon compound is 0.5 parts by mass or more, it is easy to ensure the desired adhesion, while when it is 5.0 parts by mass or less, the adhesion to the other resin layer to be bonded is not too strong, and it is easy to peel off when peeling is required.

[0155] (wax) The release layer may contain a wax as a release agent. The wax is selected from natural waxes, synthetic waxes, and wax mixtures thereof. Natural waxes include vegetable waxes, animal waxes, mineral waxes, and petroleum waxes. Examples of vegetable waxes include candelilla wax, carnauba wax, rice wax, wood wax, and jojoba oil. Examples of animal waxes include beeswax, lanolin, and whale wax. Examples of mineral waxes include montan wax, ozokerite, and ceresin. Examples of petroleum waxes include paraffin wax, microcrystalline wax, and petrolatum. Examples of synthetic waxes include synthetic hydrocarbons, modified waxes, hydrogenated waxes, fatty acids, acid amides, amines, imides, esters, and ketones. Examples of synthetic hydrocarbons include Fischer-Tropsch wax (also known as Sasol wax) and polyethylene wax, as well as the following low molecular weight polymers (specifically, polymers with a number average molecular weight of 500 to 20,000): polypropylene, ethylene-acrylic acid copolymers, polyethylene glycol, polypropylene glycol, and block or grafted polyethylene glycol and polypropylene glycol. Examples of modified waxes include montan wax derivatives, paraffin wax derivatives, and microcrystalline wax derivatives. The derivatives here are compounds obtained by any of the following processes, or a combination of them: purification, oxidation, esterification, and saponification. Examples of hydrogenated waxes include hydrogenated castor oil and hydrogenated castor oil derivatives.

[0156] Among the above, from the viewpoint of stable properties, synthetic waxes are preferred, among which polyethylene waxes are more preferred, and oxidized polyethylene waxes are even more preferred. The number average molecular weight of the synthetic wax is preferably in the range of 500 to 30,000, more preferably 1,000 to 15,000, and even more preferably 2,000 to 8,000, from the viewpoints of stability of properties such as blocking and ease of handling.

[0157] (Melamine compounds) The release layer may also contain a melamine compound as a release agent. The melamine compound is not particularly limited, but may be a melamine-based resin. Examples of the melamine resin include melamine formaldehyde resin, methylated melamine formaldehyde resin, butylated melamine formaldehyde resin, etherified melamine formaldehyde resin, epoxy-modified melamine formaldehyde resin, urea melamine resin, and acrylic melamine resin. In particular, alkyl melamine formaldehyde resin, especially butylated melamine formaldehyde resin, is preferred because of its excellent release performance.

[0158] <Crosslinking agent> When forming the release layer, it is preferable to use various crosslinking agents in combination in order to strengthen the release layer and stabilize the performance such as water repellency. It is particularly preferable to use a polyether group-containing silicone compound in combination.

[0159] As the crosslinking agent, a conventionally known material can be used. For example, melamine compounds, epoxy compounds, oxazoline compounds, isocyanate compounds, carbodiimide compounds, silane coupling compounds, hydrazide compounds, aziridine compounds, etc. can be mentioned. Among them, melamine compounds, epoxy compounds, isocyanate compounds, oxazoline compounds, carbodiimide compounds, and silane coupling compounds are preferred, and further, from the viewpoint of being able to appropriately maintain water repellency and to strengthen the release layer, melamine compounds, oxazoline compounds, and isocyanate compounds are preferred, and melamine compounds are particularly preferred. These crosslinking agents may be used alone or in combination of two or more.

[0160] The melamine compound is a compound having a melamine skeleton in the compound, and for example, an alkylolated melamine derivative, a compound partially or completely etherified by reacting an alkylolated melamine derivative with an alcohol, and a mixture thereof can be used. As the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. are preferably used. In addition, the melamine compound may be either a monomer or a polymer of dimer or more, or a mixture thereof may be used. In consideration of reactivity with various compounds, it is preferable that the melamine compound contains a hydroxyl group. Furthermore, melamine may be partially co-condensed with urea or the like, and a catalyst may be used to increase the reactivity of the melamine compound.

[0161] The oxazoline compound is a compound having an oxazoline group in the molecule, and is preferably a polymer containing an oxazoline group. The oxazoline compound can be obtained by polymerization of an addition-polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of the addition-polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline, and one of these can be used alone or two or more can be used in combination. Among these, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially. The other monomer is not limited as long as it is a monomer that can be copolymerized with the addition-polymerizable oxazoline group-containing monomer. For example, (meth)acrylic acid esters such as alkyl (meth)acrylate (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid, and salts thereof (sodium salt, potassium salt, ammonium salt, tertiary amine salt, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl (meth)acrylamide, N,N-dialkyl (meth)acrylamide, ... Examples of the alkyl group include unsaturated amides such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One of these monomers may be used alone, or two or more of them may be used in combination.

[0162] The amount of oxazoline groups in the oxazoline compound is preferably in the range of 0.5 to 10 mmol / g, more preferably 1 to 9 mmol / g, further preferably 3 to 8 mmol / g, and particularly preferably 4 to 6 mmol / g. By using the compound in the above range, it becomes easy to adjust the water repellency.

[0163] The isocyanate compound is a compound having an isocyanate or an isocyanate derivative structure, such as a blocked isocyanate. Examples of the isocyanate include aromatic isocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. Further, polymers and derivatives of these isocyanates such as biuretized products, isocyanurate products, uretdione products, carbodiimide modified products, etc. may also be used alone or in combination of two or more kinds. Among the above-mentioned isocyanates, aliphatic isocyanates or alicyclic isocyanates are more preferable than aromatic isocyanates in order to prevent yellowing due to ultraviolet light.

[0164] When used in the form of blocked isocyanate, examples of the blocking agent include bisulfites, phenolic compounds such as phenol, cresol, and ethylphenol, alcoholic compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol, active methylene compounds such as dimethyl malonate, diethyl malonate, isobutanoyl methyl acetate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone, mercaptan compounds such as butyl mercaptan and dodecyl mercaptan, lactam compounds such as ε-caprolactam and δ-valerolactam, amine compounds such as diphenylaniline, aniline, and ethyleneimine, acid amide compounds such as acetanilide and acetic acid amide, and oxime compounds such as formaldehyde, acetaldoxime, acetoneoxime, methyl ethyl ketoneoxime, and cyclohexanoneoxime. These may be used alone or in combination of two or more. Among these, from the viewpoint of being particularly effective in reducing migration of the adhesive layer to the adherend, an isocyanate compound blocked with an active methylene compound is preferred.

[0165] The isocyanate compound may be used alone or as a mixture or bond with various polymers. In order to improve the dispersibility and crosslinking property of the isocyanate compound, it is preferable to use a mixture or bond with a polyester resin or a urethane resin.

[0166] The epoxy compound is a compound having an epoxy group in the molecule. Examples of the epoxy compound include condensation products of epichlorohydrin with a hydroxyl group or an amino group of ethylene glycol, polyethylene glycol, glycerin, polyglycerin, bisphenol A, etc., polyepoxy compounds, diepoxy compounds, monoepoxy compounds, glycidylamine compounds, etc. Examples of polyepoxy compounds include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether. Examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Examples of monoepoxy compounds include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether, and examples of glycidylamine compounds include N,N,N',N'-tetraglycidyl-m-xylylenediamine and 1,3-bis(N,N-diglycidylamino)cyclohexane.

[0167] Among them, polyether-based epoxy compounds are preferred from the viewpoint of various favorable properties. In terms of the amount of epoxy groups, polyepoxy compounds having three or more functional groups are more preferred than those having two functional groups.

[0168] The carbodiimide compound is a compound having one or more carbodiimide or carbodiimide derivative structures in the molecule. For better strength of the release layer, a polycarbodiimide compound having two or more in the molecule is more preferable.

[0169] The carbodiimide compound can be synthesized by a conventionally known technique, and is generally synthesized by a condensation reaction of a diisocyanate compound. The diisocyanate compound is not particularly limited, and either aromatic or aliphatic diisocyanates can be used.Specific examples include tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexanediyl diisocyanate, and dicyclohexylmethane diisocyanate.

[0170] Furthermore, within the scope of the present invention, in order to improve the water solubility or water dispersibility of the polycarbodiimide-based compound, a surfactant or a hydrophilic monomer such as a polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkylsulfonate may be added.

[0171] A silane coupling compound is an organosilicon compound that has an organic functional group and a hydrolyzable group such as an alkoxy group in one molecule. For example, epoxy group-containing compounds such as 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; vinyl group-containing compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; styryl group-containing compounds such as p-styryltrimethoxysilane and p-styryltriethoxysilane; (meth)acrylic group-containing compounds such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)- 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane and other amino group-containing compounds; tris(trimethoxysilylpropyl)isocyanurate, tris(triethoxysilylpropyl)isocyanurate and other isocyanurate group-containing compounds; 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane and other mercapto group-containing compounds.

[0172] Among the above compounds, from the viewpoint of the strength of the release layer, epoxy group-containing silane coupling compounds, double bond-containing silane coupling compounds such as vinyl groups and (meth)acrylic groups, and amino group-containing silane coupling compounds are more preferred.

[0173] Furthermore, since these crosslinking agents are used in a design that causes them to react during the drying process or film formation process to improve the performance of the release layer, it can be assumed that unreacted crosslinking agents, reacted compounds, or a mixture of these are present in the formed release layer.

[0174] <Various polymers> In forming the release layer, various polymers such as polyester resin, acrylic resin, urethane resin, vinyl resin, etc. can be used to improve the coating appearance and transparency, and to control water repellency and slippage. Among various polymers, polyester resin, acrylic resin, urethane resin, and vinyl resin are preferred from the viewpoint of easy control of water repellency, and polyester resin and acrylic resin are more preferred.

[0175] The polyester resin may be composed of, for example, the following polyvalent carboxylic acid and polyvalent hydroxy compound as main components. That is, as the polyvalent carboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof may be used, and as the polyvalent hydroxy compound, Examples of the usable compounds include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. One or more of these compounds may be appropriately selected and a polyester resin may be synthesized by a conventional polycondensation reaction.

[0176] An acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers (hereinafter, acrylic and methacrylic may be collectively abbreviated as (meth)acrylic). These may be homopolymers or copolymers, or copolymers with polymerizable monomers other than acrylic and methacrylic monomers.

[0177] Also included are copolymers of the above polymers with other polymers (e.g., polyester, polyurethane, etc.). For example, block copolymers and graft copolymers. Alternatively, polymers (or mixtures of polymers, as the case may be) obtained by polymerizing a polymerizable monomer in a polyester solution or polyester dispersion are also included. Similarly, polymers (or mixtures of polymers, as the case may be) obtained by polymerizing a polymerizable monomer in a polyurethane solution or polyurethane dispersion are also included. Similarly, polymers (or mixtures of polymers, as the case may be) obtained by polymerizing a polymerizable monomer in another polymer solution or dispersion are also included.

[0178] The polymerizable monomer is not particularly limited, but representative compounds include, for example, various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyl fumarate, and monobutyl hydroxy itaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, Examples of such compounds include various (meth)acrylic acid esters such as lauryl (meth)acrylate; various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-methylol acrylamide, or (meth)acrylonitrile; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, and vinyl toluene; various vinyl esters such as vinyl propionate and vinyl acetate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.

[0179] A urethane resin is a polymeric compound that has urethane bonds in its molecules. Usually, urethane resins are obtained by reacting polyol with isocyanate. Examples of the polyol include polycarbonate polyols, polyester polyols, polyether polyols, polyolefin polyols, and acrylic polyols. These compounds may be used alone or in combination.

[0180] Polycarbonate polyols are obtained by dealcoholization reaction between polyhydric alcohols and carbonate compounds. Examples of polyhydric alcohols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane, etc. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, etc. Examples of polycarbonate-based polyols obtained from these reactions include poly(1,6-hexylene) carbonate, poly(3-methyl-1,5-pentylene) carbonate, and the like.

[0181] Examples of polyester polyols include polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their acid anhydrides and polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 2-methyl-1,3-propanediol, 1,6 ... 2-ethyl-2,4-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, lactonediols, etc.

[0182] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.

[0183] Examples of polyisocyanate compounds used to obtain urethane resins include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate, aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate, aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate, and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate. These may be used alone or in combination.

[0184] A chain extender may be used when synthesizing the urethane resin. The chain extender is not particularly limited as long as it has two or more active groups that react with an isocyanate group, and generally, a chain extender having two hydroxyl groups or two amino groups can be mainly used.

[0185] Examples of chain extenders having two hydroxyl groups include glycols such as aliphatic glycols, such as ethylene glycol, propylene glycol, and butanediol; aromatic glycols, such as xylylene glycol and bishydroxyethoxybenzene; and ester glycols, such as neopentyl glycol hydroxypivalate. Examples of chain extenders having two amino groups include aromatic diamines such as tolylenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propylenediamine, hexanediamine, 2,2-dimethyl-1,3-propanediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, isopropylidenecyclohexyl-4,4'-diamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.

[0186] The urethane resin may be a solvent-based resin, but is preferably a water-based resin. To disperse or dissolve the urethane resin in water, there are a forced emulsification type using an emulsifier, a self-emulsification type in which a hydrophilic group is introduced into the urethane resin, or a water-soluble type. In particular, a self-emulsification type in which an ionic group is introduced into the structure of the urethane resin to form an ionomer is preferred, since it has excellent storage stability of the liquid and excellent water resistance and transparency of the resulting release layer.

[0187] Examples of the ionic group to be introduced include a carboxyl group, sulfonic acid, phosphoric acid, phosphonic acid, and quaternary ammonium salts, with the carboxyl group being preferred. Various methods can be used to introduce carboxyl groups into urethane resins at each stage of polymerization reaction. For example, there is a method of using a resin having carboxyl groups as a copolymerization component during prepolymer synthesis, or a method of using a component having carboxyl groups as one component of polyol, polyisocyanate, chain extender, etc. In particular, a method of using a carboxyl group-containing diol and introducing a desired amount of carboxyl groups depending on the amount of this component is preferred. For example, dimethylolpropionic acid, dimethylolbutanoic acid, bis-(2-hydroxyethyl)propionic acid, bis-(2-hydroxyethyl)butanoic acid, etc. can be copolymerized with the diol used in the polymerization of the urethane resin. In addition, the above carboxyl groups are preferably neutralized with ammonia, amines, alkali metals, inorganic alkalis, etc. to form salts. Particularly preferred are ammonia, trimethylamine, and triethylamine. In such polyurethane resins, the carboxyl groups from which the neutralizing agent is removed in the drying process after coating can be used as crosslinking reaction points with other crosslinking agents, which makes it possible to provide excellent stability in the liquid state before coating, and to further improve the durability, solvent resistance, water resistance, blocking resistance, etc. of the resulting release layer.

[0188] <Antistatic agent> It is also a preferred embodiment that the release layer contains an antistatic agent to function as an antistatic release layer, thereby preventing defects caused by peeling electrification of the film or adhesion of surrounding dirt and the like caused by frictional electrification. The antistatic agent contained in the release layer is not particularly limited, and any conventionally known antistatic agent can be used. It is preferable to use a polymer type antistatic agent because of its good heat resistance and moist heat resistance. Examples of polymer-type antistatic agents include compounds having an ammonium group, polyether compounds, compounds having a sulfonic acid group, betaine compounds, conductive polymers, and the like.

[0189] The compound having an ammonium group is a compound having an ammonium group in the molecule, and examples thereof include ammonium compounds of aliphatic amines, alicyclic amines, and aromatic amines. The compound having an ammonium group is preferably a polymeric compound having an ammonium group, and the ammonium group is preferably a structure incorporated in the main chain or side chain of the polymer, not as a counter ion. For example, a polymeric compound having an ammonium group obtained by polymerizing a monomer containing an addition polymerizable ammonium group or a precursor of an ammonium group such as an amine can be mentioned, and is preferably used. The polymer may be a monomer containing an addition polymerizable ammonium group or a precursor of an ammonium group such as an amine, which is polymerized alone, or may be a copolymer of a monomer containing the addition polymerizable ammonium group or a precursor of an ammonium group such as an amine and another monomer.

[0190] Among the polymer compounds having an ammonium group, a polymer compound having a pyrrolidinium ring is also preferred because of its excellent antistatic properties and heat resistance stability.

[0191] The two substituents bonded to the nitrogen atom of the polymer compound having a pyrrolidinium ring are not particularly limited, but each is independently an alkyl group, a phenyl group, etc., and these alkyl groups and phenyl groups may be substituted with the groups shown below. Substitutable groups include, for example, a hydroxyl group, an amide group, an ester group, an alkoxy group, a phenoxy group, a naphthoxy group, a thioalkoxy group, a thiophenoxy group, a cycloalkyl group, a trialkylammonium alkyl group, a cyano group, and a halogen. In addition, the two substituents bonded to the nitrogen atom may be chemically bonded, for example, -(CH2) m -(m = an integer of 2 to 5), -CH(CH3)CH(CH3)-, -CH=CH-CH=CH-, -CH=CH-CH=N-, -CH=CH-N=CH-, -CH2OCH2-, -(CH2)2O(CH2)2- and the like.

[0192] The polymer having a pyrrolidinium ring can be obtained by cyclic polymerization of a diallylamine derivative using a radical polymerization catalyst. The polymerization can be carried out by a known method using a polymerization initiator such as hydrogen peroxide, benzoyl peroxide, or tertiary butyl peroxide in a polar solvent such as water or methanol, ethanol, isopropanol, formamide, dimethylformamide, dioxane, or acetonitrile as a solvent, but is not limited thereto. In the present invention, a diallylamine derivative and a compound having a polymerizable carbon-carbon unsaturated bond may be used as copolymerization components.

[0193] The polymer compound having an ammonium group is preferably a polymer having a structure represented by the following general formula (4) in that it has excellent antistatic properties and moisture and heat resistance stability. The polymer may be a homopolymer or copolymer, or may be copolymerized with a plurality of other components.

[0194] [ka]

[0195] For example, in the above formula (4), R 1 represents a hydrogen atom or a hydrocarbon group such as an alkyl group or a phenyl group having 1 to 20 carbon atoms, and R 2 represents -O-, -NH- or -S-, and R 3 represents an alkylene group having 1 to 20 carbon atoms or another structure capable of forming the structure of general formula (4), R 4 , R 5 and R 6 each independently represents a hydrogen atom, a hydrocarbon group such as an alkyl group having 1 to 20 carbon atoms, a phenyl group, or a hydrocarbon group having a functional group such as a hydroxyalkyl group; X - indicates various counter ions.

[0196] Among the above, from the viewpoint of particularly excellent antistatic properties and moisture and heat resistance stability, R 1 is preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and R3 is preferably an alkylene group having 1 to 6 carbon atoms, and R 4 , R 5 , R 6 are each preferably independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and R 4 , R 5 , R 6 It is more preferable that any one of the substituents is a hydrogen atom and the other substituent is an alkyl group having 1 to 4 carbon atoms.

[0197] Examples of anions that serve as counter ions to the ammonium groups of the above-mentioned ammonium group-containing polymer compound include halogen ions, sulfonates, phosphates, nitrates, alkylsulfonates, and carboxylates.

[0198] The number average molecular weight of the polymer compound having an ammonium group is not particularly limited, but is usually 1000 to 500000, preferably 2000 to 350000, and more preferably 5000 to 200000. When the molecular weight is 1000 or more, the strength of the coating film is sufficient and heat resistance stability is maintained. In addition, when the molecular weight is 500000 or less, the viscosity of the coating liquid is low, and the handling and coating properties are good.

[0199] Examples of the polyether compound include polyethylene oxide, polyether ester amide, and acrylic resins having polyethylene glycol in the side chain.

[0200] The compound having a sulfonic acid group refers to a compound that contains sulfonic acid or a sulfonate in the molecule. For example, a compound that contains a large amount of sulfonic acid or a sulfonate, such as polystyrene sulfonic acid, is preferably used.

[0201] The betaine compound may be a quaternary ammonium salt. For example, alkyl carbobetaine, alkyl sulfobetaine, alkyl amido hydroxy sulfobetaine, alkyl amido amine type betaine, alkyl imidazoline type betaine, etc. are listed. Among them, alkyl sulfobetaine is preferable.

[0202] Examples of conductive polymers include polythiophenes, polyanilines, polypyrroles, polyacetylenes, etc. Among them, polythiophenes, such as poly(3,4-ethylenedioxythiophene) used in combination with polystyrenesulfonic acid, are preferably used. Conductive polymers are more suitable than the other antistatic agents mentioned above in that they have a low resistance, but on the other hand, in applications where coloring or cost is a concern, it is necessary to take measures such as reducing the amount of use.

[0203] Furthermore, within the scope of the present invention, the release layer may contain, as necessary, antifoaming agents, coating property improvers, thickeners, organic lubricants, ultraviolet absorbers, antioxidants, foaming agents, dyes, pigments, etc.

[0204] <Ratio of release agent> The proportion of the release agent in the release layer is not particularly limited, and the appropriate amount varies depending on the type of release agent, but is preferably 3% by mass or more, more preferably 15% by mass or more, and the upper limit is not particularly limited, but is 100% by mass. In particular, the proportion of the release agent is preferably in the range of 25 to 99% by mass. When the proportion of the release agent is 3% by mass or more, sufficient water repellency is obtained.

[0205] When a long-chain alkyl compound or a fluorine compound is used as the release agent, the content in the release layer is preferably 5% by mass or more, more preferably 15 to 99% by mass, even more preferably 20 to 95% by mass, and particularly preferably 25 to 90% by mass. By having the content of the release agent in the above range, water repellency and peelability from the adhesive layer are effectively achieved. The ratio of the crosslinking agent in the release layer is preferably 95% by mass or less, more preferably 1 to 80% by mass, further preferably 5 to 70% by mass, and particularly preferably 10 to 50% by mass. As the crosslinking agent, a melamine compound, an oxazoline compound, or an isocyanate compound is preferable, and a melamine compound is particularly preferable from the viewpoint of water repellency and strength of the release layer.

[0206] When an addition type silicone compound is used as the release agent, the proportion in the release layer is preferably 5% by mass or more, more preferably 25% by mass or more, even more preferably 50% by mass or more, and particularly preferably 70% by mass or more. The upper limit of the preferred range is 99% by mass, and more preferably 90% by mass. By making the proportion of the release agent within the above range, the water repellency and peelability from the adhesive layer are effective, and the appearance of the release layer is also good.

[0207] When using a polyether group-containing silicone as a release agent, the proportion in the release layer is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 25% by mass or more, and particularly preferably 40% by mass or more.The upper limit of the preferred range is 99% by mass, more preferably 80% by mass, and even more preferably 70% by mass.By making the proportion of the release agent within the above range, the water repellency and the peelability from the adhesive layer become effective, and the appearance of the release layer also becomes good. The proportion of the crosslinking agent is preferably 90% by mass or less, more preferably 10 to 70% by mass, and further preferably in the range of 20 to 40% by mass.

[0208] When a wax is used as a release agent, the proportion in the release layer is preferably 5% by mass or more, more preferably 10 to 90% by mass, even more preferably 20 to 80% by mass, and particularly preferably 25 to 70% by mass. By using the wax in the above range, good water repellency can be obtained. The proportion of the crosslinking agent is preferably 90% by mass or less, more preferably 10 to 70% by mass, and further preferably 20 to 50% by mass. In addition, as the crosslinking agent, a melamine compound is preferred from the viewpoint of water repellency and strength of the release layer.

[0209] <Antistatic agent ratio> When providing an antistatic release layer having antistatic properties as a release layer, the proportion of the antistatic agent varies depending on the type of antistatic agent, but is preferably in the range of 0.5 mass % or more, more preferably 3 to 90 mass %, even more preferably 5 to 70 mass %, and particularly preferably 8 to 60 mass %.

[0210] When an antistatic agent other than a conductive polymer is used as the antistatic agent, the proportion of the antistatic agent in the antistatic release layer is preferably 5% by mass or more, more preferably 10 to 90% by mass, even more preferably in the range of 20 to 70% by mass, and particularly preferably in the range of 25 to 60% by mass.

[0211] When a conductive polymer is used as an antistatic agent, its proportion in the antistatic release layer is preferably 0.5% by mass or more, more preferably 3 to 70% by mass, even more preferably 5 to 50% by mass, and particularly preferably in the range of 8 to 30% by mass.

[0212] The components in the release layer can be analyzed by, for example, TOF-SIMS, ESCA, fluorescent X-ray, IR, or other methods.

[0213] On the other hand, as an example of providing a release layer by offline coating, a case where a curable silicone resin is used will be described. As for the type of curable silicone resin, as described above, any existing curing reaction type can be used, such as a heat curable type such as an addition type or a condensation type, or an electron beam curable type such as an ultraviolet curable type, and these can be used alone or in combination of a plurality of types of curable silicone resins. There is no particular restriction on the form of application of the curable silicone resin when forming the release layer, and it can be any of a form dissolved in an organic solvent, a form of an aqueous emulsion, and a form without a solvent.

[0214] Regarding the formation of the release layer, it is preferable to prepare the release layer by preparing a solution or dispersion in a solvent of the above-mentioned series of compounds and coating the liquid, which has been adjusted to a solid content concentration of approximately 0.1 to 80% by mass, onto the film.

[0215] <Method of forming release layer> Examples of methods for forming the release layer include coating, transfer, lamination, etc. In view of ease of forming the release layer, it is preferable to form it by coating.

[0216] The coating may be carried out in-line, or off-line, in which an already produced film is coated outside the system, or a combination of both.

[0217] Examples of the coating method that can be used include gravure coating, reverse roll coating, die coating, air doctor coating, blade coating, rod coating, bar coating, curtain coating, knife coating, transfer roll coating, squeeze coating, impregnation coating, kiss coating, spray coating, calendar coating, and extrusion coating.

[0218] There are no particular limitations on the drying and curing conditions when forming a release layer on a film. In the case of a coating method, the drying temperature of the solvent such as water used in the coating liquid is preferably in the range of 70 to 150°C, more preferably 80 to 130°C, and even more preferably 90 to 120°C. The drying time is approximately 3 to 200 seconds, preferably 5 to 120 seconds.

[0219] If necessary, the heat treatment may be combined with irradiation with active energy rays such as ultraviolet rays. The surface of the laminated film on which the release layer is to be formed may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.

[0220] The laminated film of the present invention may have an adhesive layer on the surface of the release layer. There is no particular limitation on the method of providing such an adhesive layer, but there are a method of laminating an adhesive layer provided on a releasable substrate to the release layer, a method of directly applying a coating liquid containing an adhesive layer component to the release layer, and the like.

[0221] When laminating from a release base material, care must be taken to avoid air bubbles and wrinkles during lamination, but the method has the advantage that no heat or other processes are applied to the final adhesive film. When applying the adhesive layer directly, heat is applied to the film for drying and hardening, so changes in the shrinkage rate of the film may need to be considered, but the method has the advantage that the adhesive layer obtained is uniform. In general, the method can be selected appropriately depending on the configuration and purpose of the final product.

[0222] [Average surface roughness of the cured resin layer surface (arithmetic mean height; Sa) and maximum peak height (Sp)] The arithmetic mean height (Sa) of the cured resin layer surface of the laminate film of the present invention must be 500 nm or more. If the arithmetic mean height (Sa) is less than 500 nm, water or bubbles are not sufficiently removed when the laminate film of the present invention is attached to an adherend, or air is not sufficiently removed when the laminate film of the present invention has an adhesive layer. From the above viewpoints, it is more preferable that the arithmetic mean height (Sa) of the cured resin layer surface is 1000 nm or more. On the other hand, from the viewpoint of damage and falling off of the uneven portion, the arithmetic mean height (Sa) is preferably 2000 nm or less. The maximum peak height (Sp) of the cured resin layer surface of the laminate film is preferably 10,000 nm or more. If it is 10,000 nm or more, the reproducibility of the response shape transfer is sufficient when the laminate film is attached to an adherend. From the above viewpoints, the maximum peak height (Sp) of the cured resin layer surface is preferably 11,000 nm or more, and more preferably 13,000 nm or more. On the other hand, from the viewpoint of damage and falling off of uneven parts, it is preferably 20,000 nm or less. The arithmetic mean height (Sa, ISO 25178 surface texture) is a parameter that expands Ra (arithmetic mean height of lines) to a surface, and is a numerical value that represents the average of the absolute value of the difference in height of each point with respect to the average surface of the surface. The maximum peak height (Sp, ISO 25178 surface texture) is a three-dimensional expansion of the two-dimensional maximum peak height (Rp), and is the maximum height from the surface with a height of 0 in the measurement area.

[0223] [Protrusion height (X) and number of protrusions (Y)] The laminated film of the present invention requires that the cured resin layer satisfies the following formula (1) in a distribution curve, the horizontal axis of which is the protrusion height (X) and the vertical axis of which is the common logarithm value log(Y) of the number of protrusions (Y), obtained from a surface profile obtained by observing the surface of the cured resin layer with a white light interference microscope (white light interferometer). The horizontal axis in the distribution curve was set as follows. That is, when observed with a white light interference microscope (white light interferometer), of the protrusions seen from a reference plane obtained from the heights measured at each measurement point, the side of the base film (A) is set as a recess and the opposite side of the recess is set as a protrusion, and the protrusion height of the protrusion is set as a positive protrusion height and the protrusion height of the recess is set as a negative protrusion height, to set the horizontal axis.

number

[0224] From the above viewpoints, the value of the above formula (1) is preferably -0.25 or more, and more preferably -0.19 or more. The upper limit is theoretically less than 0 and is not otherwise particularly limited, but from the viewpoints of the difficulty of designing the laminated film and the manufacturing costs, it is preferably -0.05 or less, and more preferably -0.10 or less.

[0225] The laminated film of the present invention requires that the surface of the cured resin layer satisfies the above formula (1), but it is preferable that the surface of the cured resin layer satisfies the following formula (2) in the above distribution curve. By satisfying formula (2), a better uneven shape can be transferred to the adherend.

number

[0226] From the viewpoint of transferring a good uneven shape to an adherend, the value of the above formula (2) is preferably −1.70 or more, more preferably −1.60 or more, even more preferably −1.50 or more, and particularly preferably −1.48 or more.

[0227] The surface of the cured resin layer of the laminate film of the present invention must satisfy the above formula (1), but further preferably has a difference (Ah) of 4 μm or more between the positive protrusion height and the negative protrusion height when the number of protrusions is 85% of the maximum, and a difference (Bh) of 7 μm or more between the positive protrusion height and the negative protrusion height when the number of protrusions is 20% of the maximum, and also satisfies the following formula (3):

number

[0228] As shown in Figures 1 to 5, the present invention is characterized in that it focuses on both the upper and lower uneven shapes with respect to a reference plane of a three-dimensional bird's-eye view obtained by observing the surface of a cured resin layer with a white light interference microscope. Normally, it is common to consider only the shape of the upper side (positive side) with respect to the reference plane, but as shown in Figure 5, in the present invention, the shape of the lower side (negative side) is also taken into consideration, and the surface condition is comprehensively considered to optimize the uneven shape of the cured resin layer surface. Furthermore, by focusing on the distribution of protrusion height and number of protrusions, it was found that the number of protrusions gradually decreased with an increase in the positive protrusion height from the reference surface. This point is also a major difference from conventional products, such as types with particles kneaded into them.

[0229] [Air release index] The air release index of the surface of the cured resin layer is preferably 5000 seconds or less, more preferably 3000 seconds or less, further preferably 2000 seconds or less, and particularly preferably 700 seconds or less. By satisfying the above range, air can be quickly released through the gap, which indicates that the shape allows air to escape easily. In the present invention, the lower limit of the air release index is not particularly limited, but is, for example, 20 seconds or more, preferably 30 seconds or more. When the lower limit of the air release index is equal to or more than the lower limit, for example, falling off of particles from the surface of the cured resin layer during processing can be suppressed. The air release index can be measured by the method described in the Examples.

[0230] <Adhesive layer> In an embodiment in which the laminated film of the present invention is a release film, the release film can be suitably used as a film for protecting an adhesive layer, which is preferably at least one selected from the group consisting of a silicone adhesive layer, an acrylic adhesive layer, and a urethane adhesive layer.

[0231] (Silicone adhesive layer) The silicone adhesive layer can be formed using the silicone adhesive described below. The silicone adhesive constituting the silicone-based adhesive layer may be any adhesive containing silicone as a main component resin. Here, the term "main component resin" refers to the resin that has the largest content (mass) among the resins that make up the adhesive. Although not particularly limited, for example, it is a resin that occupies 50 mass% or more, particularly 70 mass% or more, and of these, 80 mass% or more (including 100 mass%) of the resins that make up the adhesive. Examples of silicone adhesives include addition reaction type, peroxide curing type, and condensation reaction type silicone adhesives. Among them, addition reaction type silicone adhesives are preferred from the viewpoint of being curable at low temperature in a short time. The addition reaction type silicone adhesive is cured when forming an adhesive layer on a support. When an addition reaction type silicone adhesive is used as the silicone adhesive, the silicone adhesive may contain a catalyst such as a platinum catalyst. For example, the addition reaction type silicone adhesive can be prepared by adding a catalyst such as a platinum catalyst to a silicone resin solution diluted with a solvent such as toluene as necessary, stirring the mixture until uniform, applying the mixture to a support, and curing the mixture at 100 to 130° C. for 1 to 5 minutes. If necessary, a crosslinking agent or an additive for controlling adhesive strength may be added to the addition reaction type silicone adhesive. Alternatively, a primer treatment may be applied to the substrate film before the adhesive layer is formed.

[0232] Commercially available silicone resins for use in addition reaction type silicone pressure sensitive adhesives include, for example, SD4580PSA, SD4584PSA, SD4585PSA, SD4587LPSA, SD4560PSA, SD4570PSA, SD4600FCPSA, SD4593PSA, DC7651ADHESIVE, DC7652ADHESIVE, LTC-755, LTC-310 (all manufactured by Dow Corning Toray Co., Ltd.), KR-3700, KR-3701, KR-3704, X-40-3237-1, X-40-3240, Examples of suitable antibacterial agents include X-40-3291-1, X-40-3229, X-40-3323, X-40-3306, X-40-3270-1 (all manufactured by Shin-Etsu Chemical Co., Ltd.), AS-PSA001, AS-PSA002, AS-PSA003, AS-PSA004, AS-PSA005, AS-PSA012, AS-PSA014, PSA-7465 (all manufactured by Arakawa Chemical Industries Co., Ltd.), TSR1512, TSR1516, TSR1521 (all manufactured by Momentive Performance Materials, Inc.), and the like.

[0233] (Acrylic adhesive layer) The acrylic adhesive layer can be formed using the acrylic adhesive described below. The acrylic adhesive constituting the acrylic adhesive layer may be an adhesive containing a (meth)acrylic ester (co)polymer as a main component resin. The meaning of "main component resin" is as described above. The acrylic pressure-sensitive adhesive can be formed from a pressure-sensitive adhesive composition that further contains a photopolymerization initiator, a crosslinking agent, a silane coupling agent, and other materials, in addition to the (meth)acrylic acid ester (co)polymer, as necessary. The acrylic adhesive layer can be formed from a conventionally known adhesive composition, and for example, an adhesive composition described in JP 2019-210446 A or the like may be used.

[0234] (Urethane adhesive layer) The urethane-based adhesive layer can be formed using a urethane-based adhesive described below. The urethane adhesive constituting the urethane adhesive layer may be an adhesive containing a urethane base polymer as a main component resin. The meaning of "main component resin" is as described above. As the urethane-based base polymer of the urethane-based pressure-sensitive adhesive, a reaction product of a polyol and a polyisocyanate compound can be used. Examples of the polyol component include polymer-type polyols such as polyester polyols, polyether polyols, polycarbonate polyols, caprolactone polyols, etc. These polyol components may be used alone or in combination of two or more kinds. Examples of the polyisocyanate compound include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates. These polyisocyanate compounds may be used alone or in combination of two or more.

[0235] (Adhesive layer thickness) The thickness of the adhesive layer (after drying) is preferably 1 to 100 μm, more preferably 5 to 80 μm, further preferably 10 to 60 μm, and particularly preferably 20 to 50 μm. When the adhesive strength is equal to or greater than the above lower limit, sufficient adhesive strength is obtained, and when the adhesive strength is equal to or less than the above upper limit, handling is easy.

[0236] (Total thickness of release film with adhesive layer) In the present invention, the total thickness of the release film with the adhesive layer is preferably 500 μm or less, more preferably 40 μm or more and 350 μm or less, even more preferably 40 μm or more and 200 μm or less, and even more preferably 50 μm or more and 150 μm or less, from the viewpoint of handleability.

[0237] [Film laminate] In one aspect of the present invention, a film laminate is provided, which comprises the above laminate film and an adhesive layer on the surface of the cured resin layer of the laminate film. The film laminate basically has a structure of a base film / curable resin layer / adhesive layer. The base film, the cured resin layer and the adhesive layer are as described above. In another aspect of the present invention, a film laminate having an adhesive layer on the surface of the release film is provided. The film laminate basically has a structure of a base film / curable resin layer / release layer / adhesive layer. The base film, the cured resin layer, the release layer and the adhesive layer are as described above.

[0238] (Base film) As described above, examples of the substrate film include resin films formed from polymers such as polyethylene, polypropylene, cycloolefin polymer (COP), polyester, polystyrene, acrylic resin, polycarbonate, polyurethane, triacetyl cellulose (TAC), polyvinyl chloride, polyethersulfone, polyamide, polyimide, and polyamideimide in the form of a film. As long as it can be made into a film, it may be a mixture of these materials (polymer blend) or a composite of structural units (copolymer). Among these, as described above, it is preferable that the substrate film is a polyester film.

[0239] The thickness of the substrate film is preferably 20 to 350 μm, more preferably 25 to 250 μm, further preferably 25 to 125 μm, particularly preferably 25 to 100 μm, and particularly preferably 25 to 60 μm.

[0240] (Arithmetic mean height (Sa) of the cured resin layer surface) In the film laminate of the present invention, the surface roughness (arithmetic mean height; Sa) of the cured resin layer surface after the release film is peeled off is required to be 500 nm or more. If the arithmetic mean height (Sa) is less than 500 nm, when the release film is peeled off from the film laminate of the present invention and the adhesive layer is attached to an adherend, moisture or bubbles remain, there is a lot of air during lamination, and this causes poor appearance, or a decrease in adhesive strength due to moisture remaining. In the present invention, by having the surface roughness of 500 nm or more, when the release film is peeled off from the film laminate of the present invention and the adhesive layer is attached to an adherend, there is little moisture or bubbles remain, and there is little air during lamination, and the above-mentioned poor appearance and decrease in adhesive strength can be significantly suppressed. From the above viewpoints, the arithmetic mean height (Sa) of the cured resin layer surface is preferably 800 nm or more, more preferably 1000 nm or more, and further preferably 1100 nm or more.

[0241] Although there is no particular limitation on the thickness of the cured resin layer, it is preferably in the range of 1 to 100 μm, more preferably 2 to 80 μm, further preferably 3 to 50 μm, and particularly preferably 3 to 30 μm. By satisfying the above range, good transfer properties and adhesive properties can be exhibited.

[0242] (Glossiness of the cured resin layer surface) The surface of the cured resin layer of the laminated film of the present invention preferably has a glossiness of 10% or less at 60 degrees. When the glossiness at 60 degrees is equal to or less than the above upper limit, the matte property is more excellent. The glossiness at 60 degrees is more preferably 9% or less, and further preferably 6% or less. In addition, the surface of the cured resin layer of the laminate film of the present invention preferably has a glossiness of 15% or less at 85 degrees. When the glossiness at 85 degrees is equal to or less than the above upper limit, the matte property is more excellent. The glossiness at 85 degrees is more preferably 10% or less, and further preferably 9% or less.

[0243] <Method of manufacturing film laminate> The method for producing the film laminate of the present invention is not particularly limited, but for example, the film laminate can be produced by laminating a base film (B) with an adhesive layer onto the release layer of the release film of the present invention. At that time, the uneven shape of the release film surface can be transferred to the adhesive layer surface and / or the base film (B).

[0244] <Application> The laminated film, release film and film laminate of the present invention can be suitably used for various transfer applications by utilizing the uneven shape of the cured resin layer. For example, it is useful as a PPF (paint protection film) for the purpose of protecting automobile paint. Alternatively, it is also useful for protecting adhesive layers. It is also useful as a wrapping film for wrapping adhesive films printed on automobiles, trucks, trains, airplanes, etc. According to the laminated film and film laminate of the present invention, even when a large-area adhesive film as described above is attached to an adherend, it has good workability and can be easily and uniformly attached to the adherend. EXAMPLES

[0245] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. The measurement and evaluation methods used in the present invention are as follows.

[0246] (1) Method for measuring intrinsic viscosity of polyester 1 g of polyester from which components incompatible with the polyester had been removed was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and measured at 30°C.

[0247] (2) Average particle size (d 50 :μm) measurement method The cumulative 50% (mass basis) value in the equivalent sphericity distribution measured using a centrifugal sedimentation type particle size distribution measuring device (SA-CP3 type manufactured by Shimadzu Corporation) was taken as the average particle size.

[0248] (3) Method for measuring number average molecular weight and weight average molecular weight Measurement was carried out using GPC (HLC-8120GPC manufactured by Tosoh Corporation) under the following conditions. Measurement conditions:TOSOH TSK-GEL GHXL-L,G4000HXL,G2000HXL Solvent: Tetrahydrofuran (THF) Column temperature: 40℃ Flow rate: 1.0ml / min Detector: RI Injection concentration: 0.2w / v% Injection amount: 0.1ml The number average molecular weight and the weight average molecular weight were calculated in terms of polystyrene.

[0249] (4) Measurement of the surface roughness of polyester film, distribution curve of the cured resin layer surface, and number of protrusions and protrusion height Using a white light interferometer (Hitachi High-Tech Science Corporation "Vert Scan" (registered trademark) R5500), the surface unevenness of the laminated film (sample) surface in an area of ​​237.65 μm × 178.25 μm was measured by optical interferometry, and the relationship between the protrusion height every 0.06 μm and the number of protrusions at each protrusion height was diagrammed and expressed as a distribution curve. The common logarithm of the number of protrusions at protrusion heights X1 μm and X2 μm was taken as log (Y1) and log (Y2). The common logarithm of the maximum number of protrusions log (Y) max, the value that is 85% of the maximum value log (Y) 85%, and the value that is 20% of the maximum value log (Y) 20% were calculated. Of the protrusions seen from the reference surface obtained from the measurement, the side of the base film (A) was designated as a recess and the side opposite the recess as a protrusion. The protrusion height of the protrusions was designated as a positive protrusion height and the protrusion height of the recess was designated as a negative protrusion height. From the distribution curve, the positive protrusion height Xmax corresponding to log(Y)max, the positive protrusion height X85% corresponding to log(Y)85%, the difference (Ah) between the positive protrusion height and the negative protrusion height when the number of protrusions was 85% of the maximum value, the difference (Bh) between the positive protrusion height and the negative protrusion height when the number of protrusions was 20% of the maximum value, the ratio of Ah to Bh (Bh / Ah), and the positive protrusion height Xmin at which the number of protrusions was zero were determined.

[0250] (5) Glossiness (60 degrees, 85 degrees) The 60 degree gloss and 85 degree gloss of the surface of the cured resin layer of the laminated film were measured using a VG-2000 manufactured by Nippon Denshoku Industries Co., Ltd.

[0251] (6) Air release index The laminated film (sample) was cut to a size of 70 mm square, and the laminated film and a polyester film with a 5 mm diameter hole in the center were laminated so that the surface of the cured resin layer of the laminated film was in contact with the polyester film, and the air release index was measured. The air release index was measured using a DigiBec smoothness tester (DB-2, manufactured by Toyo Seiki Co., Ltd.) in an atmosphere with a temperature of 23°C and a humidity of 50%RH. At this time, the pressure of the pressurizing device was 100 kPa, and a small vacuum container with a volume of 380 ml was used as the vacuum container. The time it took for 1 mL of air to flow, i.e., the time (seconds) until the pressure inside the container changed from 50.7 kPa to 48.0 kPa, was measured, and the obtained number of seconds was taken as the air release index. The smaller the air escape index value, the faster the air escapes through the gaps, indicating that the shape allows air to escape easily.

[0252] Examples and comparative examples are shown below. The polyester resins used in producing the polyester films used in the examples and comparative examples, and the cured resin compositions used to prepare the laminate films are as follows.

[0253] <Polyester resin A> Polyester resin made of polyethylene terephthalate (intrinsic viscosity: 0.85 dl / g) <Polyester resin B> Polyester resin made of copolymerized polyethylene terephthalate containing 22 mol% isophthalic acid (intrinsic viscosity: 0.70 dl / g, melting point: 198°C) <Polyester resin C> Polyester resin composition containing polyethylene terephthalate and spherical silica particles with an average particle size of 2.7 μm (intrinsic viscosity: 0.6 dl / g) <Polyester resin D> Polyester resin composition containing polyethylene terephthalate and spherical silica particles with an average particle size of 4.1 μm (intrinsic viscosity: 0.6 dl / g) <Polyester resin E> Polyester resin composition (intrinsic viscosity: 0.6 dl / g) containing polyethylene terephthalate and alkyl methacrylate-styrene copolymer particles with an average particle size of 4 μm.

[0254] <Cured resin composition> The following acrylate (A), acrylate (B), acrylate (C), acrylate (D), acrylate (E), acrylate (F), polymer (G1), polymer (G2), particle (H), and photopolymerization initiator (I) were mixed in the amounts (parts by mass, calculated as non-volatile content) shown in Tables 1 and 2 (for components other than acrylates (A) to (F), the amounts are based on 100 parts by mass of the total of the acrylate resins). Next, a mixed solvent of propylene glycol monomethyl ether (hereinafter, PGM) and methyl ethyl ketone (hereinafter, MEK) (PGM:MEK (mass ratio) 7:3) was added so that the solid content concentration was 30% by mass, and the mixture was stirred until it became uniform to obtain a curable composition (coating liquid) used in each example and comparative example.

[0255] Acrylate (A): Dicyclopentenyloxyethyl acrylate (Fancryl FA-512AS, manufactured by Showa Denko Materials Co., Ltd.)

[0256] Acrylate (B): Ethoxylated dipentaerythritol polyacrylate (A-DPH-12E, manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0257] Acrylate (C): A mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (Viscoat #300 manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0258] Acrylate (D): A mixture of a condensate of isophorone diisocyanate and dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (Mitsubishi Chemical Corporation, Shikou UV1700B)

[0259] Acrylate (E): Hyperbranched hexafunctional acrylate (Satomer CN2303)

[0260] Acrylate (F): A mixture of glycerin diacrylate and glycerin triacrylate (Aronix M-930, manufactured by Toa Gosei Co., Ltd.)

[0261] (Synthesis Example 1: Synthesis of Monomer (i-1)) Methacrylic anhydride (Tokyo Chemical Industry Co., Ltd.) was distilled under reduced pressure, and the fraction with a purity of 99.8% or more was collected to obtain a distillate of methacrylic anhydride. The reduced pressure distillation was carried out by gradually increasing the temperature from room temperature to 90° C. at a pressure of 30 Pa. Separately, 22.4 g (0.1 mol) of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (manufactured by Tokyo Chemical Industry Co., Ltd.) and 30.4 g (0.3 mol) of triethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) were dissolved in 500 mL of methylene chloride (manufactured by Tokyo Chemical Industry Co., Ltd.) To this, 23.1 g (0.15 mol) of the above-mentioned distillate of methacrylic anhydride was dropped at room temperature and stirred for 12 hours. The reaction solution was washed three times with 500 mL of ion-exchanged water, and then the organic phase was concentrated to remove the solvent. The residue was purified by column chromatography (ethyl acetate / hexane = 10 / 90 (volume ratio)) to obtain 21.6 g of the target compound (yield 74%). 1 H-NMR analysis confirmed that the compound obtained was 2-[4-(2-hydroxy-2-methyl-1-oxopropyl)phenoxy]ethyl methacrylate. 1H NMR(300MHz,Chloroform-d:δ8.06(d,J=9.0Hz,2H),6.96(d,J=9.0Hz,2H),6.13(d,J=0.6Hz,1H),5.59( s,1H),4.50(d,J=5.1Hz,2H),4.29(dd,J=5.5,4.1Hz,3H),1.94(dd,J=1.6,1.0Hz,3H),1.61(s,6H).

[0262] [Polymer having active groups capable of generating radicals upon irradiation with active energy rays] Polymer (G1) In a flask equipped with a stirrer, a condenser, and a thermometer, 75.0 parts of methyl isobutyl ketone (hereinafter referred to as MIBK) was placed and stirred. Next, the inside of the flask was replaced with nitrogen, the temperature was raised to 65°C, and a mixed solution of 40.0 parts of 4-methacryloyloxybenzophenone (manufactured by Shinryo Corporation), 10.0 parts of stearyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylate S), 10.0 parts of N,N-diethylaminoethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylate DE), 30.0 parts of 2-ethylhexyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylate EH), 30.0 parts of 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acrylate HO), 0.8 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., trade name: V-65), and 75.9 parts of MIBK was added dropwise over 2 hours. After another 2 hours, in order to increase the polymerization rate, a mixture of 0.5 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., product name: V-65) and 1.0 parts of MIBK was added and held for 5 hours. Thereafter, the reaction solution was cooled to 40°C to polymerize a polymer (G1) having an active group that generates radicals when irradiated with active energy rays. The non-volatile content of G1 was 40%, and the weight average molecular weight (Mw) was 16,700. The composition and evaluation results are shown in Table 1.

[0263] ·Polymer (G2) In a flask equipped with a stirrer, a condenser, and a thermometer, 89.2 parts of propylene glycol monomethyl ether acetate (hereinafter referred to as PMA), 36.1 parts of the monomer (i-1) obtained in Synthesis Example 1, 31.5 parts of 2-(perfluorohexyl)ethyl methacrylate (manufactured by Daikin Industries, Ltd., product name: C6SFMA monomer), 7.0 parts of 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name: Acryester HO), 4.9 parts of glycidyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name: Acryester G), and 0.4 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., product name: V-65) were placed and stirred. Next, the flask was replaced with nitrogen and heated to 90°C, and a mixed solution of 15.5 parts of the monomer (i-1) obtained in Synthesis Example 1, 13.5 parts of 2-(perfluorohexyl)ethyl methacrylate (manufactured by Daikin Industries, Ltd., trade name: C6SFMA monomer), 3.0 parts of 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acryester HO), 2.1 parts of glycidyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: Acryester G), and 57.1 parts of PMA was dropped over 4 hours. After another 2 hours, in order to increase the polymerization rate, a mixed solution of 1.2 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., trade name: V-65) and 6.0 parts of PMA was added and held for 5 hours. Thereafter, the reaction solution was cooled to 40°C, and 84.5 parts of PMA was added and stirred to polymerize a polymer (G2) having an active group that generates radicals by irradiation with active energy rays. The non-volatile content of G2 was 30%, and the weight average molecular weight (Mw) was 110900. The composition and evaluation results are shown in Table 1.

[0264] Particles (H): Cross-linked acrylic particles with an average particle size of 1.8 μm (MX-180TA manufactured by Soken Chemical Industries, Ltd.)

[0265] Photopolymerization initiator (I): Omnirad 184 (manufactured by IGM Resins BV)

[0266] Example 1 The polyester resin A and the polyester resin C in an amount such that the particle addition amount was 0.4% by mass were each fed into a vented twin-screw extruder. Each was melted at 285°C, co-extruded from a die, and cooled and solidified on a cooling roll with a surface temperature set to 22°C using an electrostatic application adhesion method to obtain an unstretched sheet. Next, the film was stretched 3.3 times in the longitudinal direction at a temperature of 85°C using the roll peripheral speed difference, and then introduced into a tenter, stretched 4.0 times in the transverse direction at 140°C, and heat-treated at a main crystallization zone temperature of 235°C. Then, the film was relaxed 10% in the transverse direction to obtain a biaxially stretched polyester film A having a thickness of 50 μm. The surface roughness of the obtained polyester film A was 0.012 μm. Furthermore, a cured resin composition having the composition shown in Table 1 was applied to a sheet having a thickness (after drying) of 5 g / m 2 The coating was then dried at 70°C for 60 seconds. Then, excimer light (half width 14 nm) from xenon (wavelength 172 nm) was applied at an integrated light intensity of 15 mJ / cm 2 , illuminance 5mW / cm 2 The dried coating was irradiated with a xenon excimer 172 nm light irradiator (Ushio Electric Co., Ltd., lamp unit type: SUS05 (lamp house type: H0011, lighting power supply type: B0005), nitrogen flow (oxygen concentration 1% or less)). In addition, a high-pressure mercury lamp was used in the atmosphere to irradiate the dried coating with an accumulated light quantity of 400 mJ / cm. 2 , illuminance 200mW / cm 2 The substrate film was exposed to ultraviolet light using a UV conveyor of a high-output UV device (model: US5-X1802-X1202) manufactured by Eye Graphics, to obtain a laminate having a cured resin layer with an uneven structure having a thickness (after drying) of 5 μm on the substrate film.

[0267] Examples 2 to 5 and Comparative Examples 1 to 4 A laminated film was produced in the same manner as in Example 1, except that the polyester film composition was changed to the composition shown in Tables 1 and 2, the cured resin composition was changed to the composition shown in Tables 1 and 2, the excimer light irradiation process was omitted, and the film thickness was changed to 4 μm. The properties of these films are shown in Tables 3 and 4 below.

[0268] [Table 1]

[0269] [Table 2]

[0270] [Table 3] [Table 4]

[0271] From the results of Examples 1 to 5, it was found that the laminated film of the present invention has a moderately roughened surface and can be suitably used for transferring the uneven shape of the cured resin layer surface to the surface of the other adherend. It was also found that the laminated film has an uneven shape that is difficult to reproduce with conventional kneaded-in type matte films.

[0272] 1 and 2 are bird's-eye views of the surfaces of the cured resin layers of the laminate films obtained in Examples 1 and 3. From these figures, the roughness of the surfaces of the cured resin layers of the laminate films of the present invention is visually confirmed, and it is clear that the roughness is different from the film surfaces of Comparative Examples 1 and 4 (see FIGS. 3 and 4). 6 and 7 show distribution curves obtained from surface profiles obtained by observing the surfaces of the cured resin layers of the laminate films obtained in Examples 1 and 3, and Fig. 8 and Fig. 9 show distribution curves obtained from surface profiles obtained by observing the surfaces of the cured resin layers of the laminate films obtained in Comparative Examples 1 and 4, using a white light interference microscope. It is clear from Figs. 6 to 9 that the shapes of the distribution curves are significantly different between the Examples and the Comparative Examples. For example, Example 3 and Comparative Example 2 have different configurations of the cured resin composition. Example 3 is characterized in that the blending ratio of acrylate with a small number of functional groups is low, and the cured resin layer has a moderate hardness while also having a moderate flexibility, so that the surface of the cured resin layer easily follows deformation and is designed to easily form unevenness. On the other hand, Comparative Example 2 has a too high blending ratio of acrylate including urethane acrylate, so the cured resin layer is too soft and there is no opportunity to form convex portions, which is presumably why it is difficult to form unevenness.

[0273] Although the details of the mechanism of unevenness formation are unclear, it can be assumed as follows. For example, in the reaction process for curing the curable resin composition, the hard component (e.g., a polyfunctional acrylate having three or more functional groups) cures first to form a film, and the soft component (e.g., a urethane acrylate) is deformed by the presence of the hard component and pushed upward to form a convex portion. Alternatively, the soft component (e.g., a urethane acrylate) cures first, and the hard component (e.g., a polyfunctional acrylate having three or more functional groups) climbs up onto the soft component to form a convex portion. From the above, it is believed that the desired uneven structure can be appropriately formed by providing an appropriate hardness to the cured resin layer. [Industrial Applicability]

[0274] The laminated film of the present invention is suitable for applications requiring transfer of a concave-convex shape (for example, for protecting automobile paintwork or as a wrapping film).

Claims

1. A cured resin layer is provided on one surface of a base film (A), the cured resin layer has an uneven structure, and the arithmetic mean height (Sa) of the surface of the cured resin layer is 500 nm or more, A laminate film, in which in a distribution curve obtained from a surface profile obtained by observing the surface of the cured resin layer with a white light interference microscope, the horizontal axis being projection height (X) and the vertical axis being the common logarithm of the number of projections (Y), the cured resin layer satisfies the following formula (1): [0010] [In the formula, log(Y)max indicates the value at which the common logarithm of the number of protrusions is maximum, and Xmax indicates the positive protrusion height when the common logarithm of the number of protrusions is maximum. log(Y)85% indicates the value at which the common logarithm of the number of protrusions is 85% of the maximum value, and X85% indicates the positive protrusion height when the common logarithm of the number of protrusions is 85% of the maximum value. "Positive protrusion height" refers to the protrusion height of the protrusions of the protrusions as viewed from the reference plane determined from the heights measured at each measurement point in the distribution curve, with the side of the base film (A) being the recess and the side opposite the recess being the protrusion.]

2. The laminate film according to claim 1 , wherein the cured resin layer satisfies the following formula (2) in the distribution curve: [0025] [In the formula, Xmin represents a positive protrusion height when the number of protrusions is 0, log(Y)85% represents a value when the common logarithm of the number of protrusions is 85% of the maximum value, and X85% represents a positive protrusion height when the common logarithm of the number of protrusions is 85% of the maximum value. The term "positive protrusion height" is as described above.]

3. 3. A laminate film according to claim 1 or 2, wherein the cured resin layer has a difference (Ah) between the positive protrusion height and the negative protrusion height when the number of protrusions is 85% of the maximum value in the distribution curve of 4 μm or more, and a difference (Bh) between the positive protrusion height and the negative protrusion height when the number of protrusions is 20% of the maximum value in the distribution curve of 7 μm or more, and satisfies the following formula (3): [0030] The "positive protrusion height" and "negative protrusion height" refer to the protrusions seen from a reference plane determined from the heights measured at each measurement point when observing the distribution curve with a white light interference microscope (white light interferometer), with the side of the base film (A) being the recess and the side opposite the recess being the protrusion, and the protrusion height of the protrusion is the positive protrusion height and the protrusion height of the recess is the negative protrusion height.

4. The laminate film according to any one of claims 1 to 3, wherein the base film (A) is a polyester film.

5. The laminate film according to any one of claims 1 to 4, wherein the base film (A) contains particles in a layer in contact with the cured resin layer.

6. The laminated film according to claim 5, wherein the particles have an average particle size of 1 to 10 μm.

7. The laminate film according to any one of claims 1 to 6, wherein the arithmetic mean height (Sa) of the base film (A) on the side on which the cured resin layer is formed is 5 nm or more.

8. The laminate film according to any one of claims 1 to 7, wherein the base film (A) has a single-layer structure.

9. The laminate film according to any one of claims 1 to 7, wherein the base film (A) has a multilayer structure consisting of at least two layers.

10. The laminate film according to any one of claims 1 to 9, wherein the maximum peak height (Sp) of the surface of the cured resin layer is 10,000 nm or more.

11. The laminated film according to any one of claims 1 to 10, wherein the gloss of the surface of the cured resin layer at 60 degrees is 10% or less.

12. The laminate film according to any one of claims 1 to 11, wherein the gloss of the surface of the cured resin layer at an angle of 85 degrees is 15% or less.

13. The laminate film according to any one of claims 1 to 12, wherein the cured resin layer is a cured product of a curable resin composition containing a (meth)acrylate.

14. The method for producing the laminate film according to any one of claims 1 to 13, comprising a step of forming the cured resin layer by excimer lamp irradiation or ultraviolet (UV) irradiation.

15. A release film comprising a cured resin layer of the laminate film according to any one of claims 1 to 13, and a release layer on the cured resin layer.

16. 16. The release film according to claim 15, wherein the release layer comprises at least one release agent selected from the group consisting of silicone compounds, melamine compounds, fluorine compounds, waxes, and long-chain alkyl compounds.

17. A film laminate comprising the release film according to claim 15 or 16 and an adhesive layer on a surface of the release layer of the release film.

18. A film laminate comprising the laminate film according to any one of claims 1 to 13 and an adhesive layer on a surface of a cured resin layer of the laminate film.

19. A transfer product having the projections and recesses on the surface of the cured resin layer of the laminate film according to any one of claims 1 to 13 transferred thereto.

20. A transfer product having the projections and recesses on the surface of the release layer of the release film according to claim 15 or 16 transferred thereto.

21. The film laminate according to claim 17 or 18, wherein the adhesive layer is at least one selected from the group consisting of an acrylic adhesive layer, a urethane adhesive layer, and a silicone adhesive layer.

22. The laminate film according to any one of claims 1 to 13, which is used for protecting an adhesive layer.

23. The release film according to claim 15 or 16, which is for protecting an adhesive layer.

24. The laminate film according to any one of claims 1 to 13 and 22, which is used for automobile paint protection or as a wrapping film.

25. The release film according to any one of claims 15, 16 and 23, which is for automobile paint protection or wrapping film.

26. 19. The film laminate according to claim 17 or 18, which is for automobile paint protection or wrapping film.

Citation Information

Patent Citations

  • Paint film protective film for automobile

    JP1995089468A

  • Peel liner having microembossed pattern

    JP2006070273A

  • Adhesive sheet

    WO2015152352A1

Cited By

  • Release film and film laminate

    JP2023177702A

  • Release film and film laminate

    JP7889077B2